Tunisie : Ouverture du tribunal de première instance à Djerba - Atoui, Yassine (Tunisie numérique, 2026)
Tunisie : Ouverture du tribunal de première instance à Djerba
Keywords: Tribunaux -- Djerba

من مسقط إلى جربة: الإباضية كفضاء مذهبي عابر للحدود - بوعبدالله, وجدان (Gulf House, 2026)
تتجاوز آفاق العلاقات بين سلطنة عُمان وتونس حدود العلاقات الدبلوماسية والاستثمار وتبادل الخبرات، لتستند إلى عمق تاريخي وثقافي ومذهبي ضارب في القدم. ثمّة قرون من الامتداد المشترك، جعلت من العلاقة بين مسقط وتونس حالة مختلفة في الفضاء العربي، علاقة تتجاو

Djerba Midoun : lancement du projet municipal “Yati Nature” pour protéger la plage contre l’érosion (Webmanagercenter, 2026)
Le coup d’envoi du projet municipal pilote &qout;yati nature&qout; pour la protection de la plage de Djerba Midoun contre l’érosion et la désertification a été donné jeudi lors d’une journée d’information. Ce projet, dont le coût est estimé à 365 mille dinars, porte notamment sur l’installa…

Musée du patrimoine traditionnel de Djerba: entre mémoire insulaire et récits du quotidien - I. R. (La Presse de Tunisie, 2026)
À l’origine, le Musée du Patrimoine Traditionnel de l’île de Djerba a trouvé refuge au sein des structures de la Zaouïa de Sidi Zitouni, à Houmt Souk. Édifié à la fin du XVIIIe siècle sous l’impulsion du caïd Hmida Ben Ayed, ce monument fut érigé pour honorer la mémoire du cheikh et juge Abou Bakr […]
Keywords: Musée -- Djerba

Spotlight on: Professor Anna Leone - Bridging ancient history and heritage preservation across North Africa (2025)
London: Durham University has issued the following news release: Professor Anna Leone is a leading authority on North African archaeology and heritage protection. Her work is driven by her fascination with ...
Keywords: Archéologie -- Djebel Nefousa

جزيرة جِربة وأثرُ نفرٍ من الجِنّ في الحياة الاجتماعية والسياسية في تونس - محجوب, أحمد (مجلة الفِراتْس, 2024)
يظهر إيمان التونسيين بالسحر ومسّ الجانّ جلياً في البرامج الحوارية على الفضائيات التونسية، وولهِ المغامرين من أصقاع البلاد بزيارة واستكشاف البقاع والديار "المسكونة". وطال هذا الأمرُ السياسةَ وقصور الحُكّام، إذ يُشاع أن زين العابدين بن علي، الرئيس الأسبق لتونس، كان يزاول مع زوجته الشعوذة والسحر. يكتب أحمد محجوب لمجلة الفِراتْس.

Can Treated Wastewater Help Algeria Overcome Water Scarcity? - Drouiche, Nadjib (2026)
The search for alternative sources of water has become a priority in Algeria, with treated wastewater being recognized as a tool for enhancing water security
Keywords: Irrigation -- Mzab

دار الجيلاني في جربة، جماليّة المعمار وصخب التراث - سليم, ضو (السفير العربي, 2025)
المشروع في جوهرهِ تجسيد واضح لمبادرة الاقتصاد الاجتماعي التضامني، التي ترمي إلى وضع استراتيجية واضحة تمكِّن من الاستغلال الأمثل للموارد المادية والبشرية، وتقاوم هنّات المنوال الليبرالي ونقائصه الفادحة على مستوى تحقيق الإدماج المهني والاجتماعي لكافة الشرائح، خاصة غير الحاصلين على الشهادات منهم.
Keywords: Architecture -- Djerba

“Djerba sans plastique” : cinq unités touristiques réduisent efficacement leur consommation - Bessais, Raja (webmanagercenter, 2025)
Un atelier s’est tenu, lundi à Djerba pour marquer la clôture de l’initiative &qout;Djerba, zone à faible utilisation de plastique à usage unique&qout;, lancée pour la première fois sur l’île il y a cinq mois. L’objectif est d’impliquer les établissements touristiques, dont des hôtels, des …
Keywords: Crises environnementales -- Djerba

The Keepers of Egyptian Recipes in the Ethereal Oasis of Siwa - Zeidy, Suzanne; Badrawi, Rawah (daftar دفتر, 2025)
Unlike other countries in the region, Egypt never had waves of emigrants go out into the world as a diaspora of ambassadors to advertise its cuisine abroad. The flavors, rituals and dishes stayed at home, and were passed down from generation
Keywords: Cuisine -- Siwa

Taieb Zayoud expose l’olivier tunisien en mosaïque en Arabie Saoudite (La Presse de Tunisie, 2025)
L’artisan Taieb Zayoud, originaire de Djerba et reconnu internationalement pour ses œuvres en mosaïque, expose actuellement une œuvre monumentale autour de l’olivier tunisien lors de la Semaine saoudienne et internationale du patrimoine et de l’artisanat. L’exposition se tient à l’université Princesse Nour bint Abdul Rahman, en Arabie Saoudite, du 20 au 27 novembre 2025. Cette
Keywords: Arts -- Djerba

Djerba-Projet « Fesguiatna »: quand 10 citernes ancestrales reprennent Vie (La Presse de Tunisie, 2025)
L'association "Jlij" pour l'environnement marin (AJEM) continue de mettre en œuvre l'un des projets environnementaux et de développement les plus importants sur l'île de Djerba : le projet "Fasquiatna" (notre citerne), visant à aménager et entretenir 10 citernes publiques pour la collecte des eaux de pluie. Ces citernes ont été identifiées dans différentes zones de
Keywords: Monuments -- conservation -- Djerba

Рукопис як інвестиція - Yakubovych, Mykhaylo (Український тиждень, 2021)
Keywords: Manuscrits -- Lviv

Matriarchs of the East African coast: Power, Property and the changing status of Women in the Swahili world (1300-1900 CE) - Samuel, Isaac (African History Extra, 2025)
Historical traditions of several pre-colonial African societies are awash with stories of titled women who played prominent roles in the continent’s political history, such as the Candaces of ancient Kush and Queen Nzinga’s dynasty in Angola.
Keywords: Vie politique -- Zanzibar

Yves Régnier, le bel oublié de la littérature française (2018)
Yves Régnier est le bel oublié de la littérature française. Son oeuvre est pourtant d'une rare qualité. Le temps de la réhabilitation est-il venu ?
Keywords: Nomadisme -- Mzab

‘Ridiculous Falsehoods’: Archival Sources on Women in Nineteenth-Century Oman - Curstaidh, Reid (Qatar Digital Library, 2022)
Archival records on the Qatar Digital Library can help to challenge traditional assumptions and paint a fuller picture regarding the role of women in nineteenth-century Oman.

Le photographe Pierre Gassin sur les traces de la berbérité à Djerba - I.B. (Kapitalis, 2025)
Pierre Gassin, photographe français résidant à Kerkennah, présente l'exposition '‘Berbérités Djerba’’, du 17 octobre au 16 novembre 2025.
Keywords: Arts -- Djerba

Vient de paraître – « De beaux détails » de Moez Naija : Petites histoires, grandes émotions - Bou Ouni, Amal (La Presse de Tunisie, 2025)
A travers ce livre, Moez Naija imagine, invente tout en se déployant dans des soucis concrets. Le style d’écriture est simple, fluide, profondément humain et fo
Keywords: Littérature -- Djerba

Djerba-Port de pêche de Houmet Souk: le mur de la discorde - Haouari, Imen (2025)
La sérénité de l'île des Lotophages a été troublée cette semaine par un mouvement de colère de la société civile et des habitants de Djerba. La raison de leur i
Keywords: Pêche -- Djerba

Justice transitionnelle : Quand les victimes racontent - Bresillon, Thierry (Inkyfada, 2015)
La répression et l’injustice des années de dictature ont pris mille visages. Quatre des personnes venues déposer leur dossier à l’IVD ont retracé leur parcours.

Modern Ibadi Books on the Move: the “al-Shaykh Mosque” Library in Houmt Souk (Djerba, Tunisia) | رحلات الكتب الإباضية الحديثة: مكتبة “جامع الشيخ” بحومة السوق (جربة، تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2025)
This summer, I have had the chance to return to Djerba (Tunisia) and work with my colleague from Ibadica, Si Mahfoudh Dahman, on documenting part of another library collection there. This month has…
Keywords: Manuscrits -- Djerba; Shaykh, mosquée al- (Houmt Souk, Djerba)

La Mosquée Al Maazouzine à Djerba retrouve son éclat d'antan - Barbirou, Cyrine (L'Economiste Maghrébin, 2025)
La mosquée Al Maazouzine à Mezraia, Djerba (gouvernorat de Médenine), a été restaurée et inaugurée après deux semaines de travaux.
Keywords: Architecture -- Djerba; Monuments -- conservation -- Djerba

Djerba : La renaissance de la mosquée de Mezraia - Bourial, Hatem (Webdo, 2025)
C'est une initiative citoyenne qui a rendu toutes ses couleurs à l'une des anciennes mosquées de Mezraia. Autour de Mouldi
Keywords: Architecture -- Djerba; Monuments -- conservation -- Djerba

Tunisians demand accountability for dual citizen who served in Israeli army during Gaza war (Middle East Monitor, 2025)
Dozens of Tunisians have demanded accountability for a Tunisian-Israeli citizen who served in the Israeli occupation army during the war on the besieged Gaza Strip. Photos and videoclips of a Tunis…
Keywords: Guerre de Gaza (2023-....); Judaïsme -- Djerba

Polémique en Tunisie : Un chanteur d’origine juive apparu en uniforme de l’armée israélienne (2025)
Le chanteur tunisien d’origine juive, identifié comme Sahi Maimoun, est au centre d’une vive controverse après la diffusion d’images le
Keywords: Guerre de Gaza (2023-....); Judaïsme -- Djerba

Sulaiman al-Baruni: life of an Ibadhi scholar and statesman in North Africa and Oman - Owtram, Francis (Untold Lives, 2024)
One of the distinctive features of Oman is that the majority of its population are adherents to the Ibadhi sect of Islam - neither Sunni nor Shi’a - which established itself in the early Islamic period on the periphery of Islamic empire and survives today in Oman and in North...
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Oman : les chrétiens peuvent librement pratiquer - Janva, Michel (Le Salon Beige, 2016)
Marc Fromager montre que dans le sultanat d'Oman, les chrétiens vivent libres : "[…] Oman est un très vieil État remontant aux premiers siècles de notre ère. La monarchie est absolue, […]
Keywords: Christianisme -- Oman

Le Corps des Djerbiennes, regard d'une anthropologue de l'île tunisienne - Aurat, Louise (medfeminiswiya.net, 2024)
Aziza Ben Tanfous, née en 1942, est témoin des grandes transformations sociétales impactant la vie des femmes ces dernières décennies sur l'île de Djerba, en Tunisie. L'anthropologue dépeint une société qui suit les évolutions de son temps, marquée par l'héritage des coutumes d'antan.
Keywords: Ben Tanfous, Aziza (1942-...); Moeurs et coutumes -- Djerba

من هو محمود قطاط؟ - بشة, سمير (2017)
ولد بجزيرة جربة في 28 مارس 1945، تونس، أستاذ متميّز بالجامعة التونسيّة، وزارة التعليم العالي والبحث العلمي، اختصاص موسيقى وعلوم موسيقيّة- حضارة عربيّة إسلاميّة. درّس بفرنسا بالمدرسة التطبيقية للدراسات العليا/قسم علم موسيقى الشعوب-جامعة باريس6 (1972-1975)، وبمركز دراسات الموسيقى الشرقية-جامعة السربون باريس 4، قسم الدراسات الإثنولوجية/ دراسات العالم الإسلامي، بجامعة باريس …
Keywords: Biographies; Musique -- Djerba

Port Marina Houmet Souk : une honte à ciel ouvert à l’aube de la saison touristique - Sghaïer, Mohamed Ali (Realités, 2025)
L’île de Djerba, récemment inscrite au patrimoine mondial de l’UNESCO pour la richesse de son architecture et la diversité de son héritage culturel, mérite tous les égards. Pourtant, à quelques jours de l’ouverture de la saison touristique, un constat accablant s’impose : le port de la Marina Houmet Souk est dans un état de délabrement...
Keywords: Crises environnementales -- Djerba

ثلاث ليال في جزيرة جربة - العبري, بدر (baderalabri.com, 2025)
جزيرة جربة من المناطق السّياحيّة الّتي يحيطها البحر من كلّ جانب، وتسمى جزيرة المساجد والأحلام، وفيها المسلمون واليهود، والمسلمون إباضيّة ومالكيّة، وهم متعايشون فيما بينهم، وفيها الأسواق القديمة، والآثار العتيقة من المساجد والمدارس والمكتبات وغيرها، وهي المنطقة السّياحيّة الأولى في تونس، وارتبطت بالإباضيّة منذ عصر الإسلام المبكر، وقد دخلها الإسلام مبكرا جدّا يقال سنة 47هـ.
Keywords: Récits de voyage -- Djerba

Which books has Saʿid al-Shammakhi (d.1883) read? Let him tell you about it. | ما هي الكتب التي قرأها سعيد الشماخي؟ دعه هو يعلمك بها - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2024)
A copy of the Kitāb al-īḍāḥ and accompanying gloss, from the Gouja family library in Djerba, Tunisia. In my recent book, the Ottoman Ibadis of Cairo, I used the library of the Ibadi trade agency, s…
Keywords: Manuscrits -- Djerba

Jean Despois, the Rockefellers & the Jebel Nafusa | الجيوغرافي الفرنسي جان دي پوا وعمله الميداني في جبل نفوسة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2025)
Sur le contexte de la mission de Jean Despois au Djebel Nefousa.
Keywords: Géographie -- Djebel Nefousa

Traditional Medicine in Oman - Ungvarsky, Janine (Ebsco Research Starters Home, 2023)
Traditional medicine in Oman is a vital aspect of the country's cultural heritage, employing a variety of plant-based remedies and techniques passed down through generations. The Omani people have a strong appreciation for their cultural practices, which include the work of traditional healers, known as hakims, who utilize knowledge acquired from family elders. These healers often draw from a rich tradition that resonates with ancient medical principles, such as the concept of balancing humors, akin to those found in Unani Tibb, an Islamic form of medicine. Omani traditional medicine incorporates around thirty-three different plants, which are transformed into various formats, including pastes, decoctions, and infusions, to treat a range of ailments from common colds to chronic conditions like diabetes. Commonly used ingredients include limes, garlic, frankincense, and ginger, among others. Despite the availability of Western medicine, many Omanis prefer traditional remedies, with studies indicating that a significant percentage relies on these methods either exclusively or alongside contemporary treatments. The government supports traditional medical practices through clinics offering free services, promoting the preservation of this invaluable aspect of Oman's identity. Techniques such as acupuncture and cupping are also employed, although plant-based treatments remain predominant. Overall, traditional medicine in Oman exemplifies a deep respect for cultural traditions and an enduring commitment to holistic health practices.
Keywords: Médecine -- Oman

Sommet de la cacophonie - Z (Debatunisie, 2022)
Keywords: Crises environnementales -- Djerba; Vie culturelle -- Djerba

Colonel Jayakar's Omani Treasures - Erdman, Michael (Asian and African studies blog, 2025)
The colophon of the Kitāb al-Dalīl featuring decoration common through the manuscript grouping. (Kitāb al-Dalīl. Oman, 17 Shawwāl 1312 AH/12 April 1895 CE). (Or 6564, f 177r). In early 2024, preparing for a visit by an Omani guest, I set out to find what Omani manuscripts we might hold. Not...
Keywords: Manuscrits -- Londres; Manuscrits -- Oman

Short Teaching Module: Global Microhistory and the Nineteenth-Century Omani Empire - Roberts, Nicholas P. (World History Commons, 2021)

How NOT to Describe People Who Are Foreign to You: Exoticizing Omanis - Risse, Marielle (Come From Away, 2024)
I know that a travel writer, excited about a culture that is new to them, might not want to go into all these kinds of details. But when the writer was in Dhofar, they saw dozens, if not hundreds, …
Keywords: Dhofar; Récits de voyage -- Oman

Djerba : Les insulaires à la rescousse pour sauver les mosquées ibadites - Haouari, Imen (2024)
Les mosquées ibadites multiséculaires de Djerba ont joué un rôle crucial dans le système défensif de l’île. Leur nombre important, leur
Keywords: Monuments -- conservation -- Djerba

«Merveilles de l’architecture religieuse - Mosquées et Zawiyas de Tunisie IXe s.-XIXe s. J.C» de Abdelaziz Daoulatli : Revisiter une facette de notre patrimoine - Haouari, Imen (2024)
C’est un magnifique livre que l’historien et chercheur Abdelaziz Daoulatli vient de publier aux éditions du Patrimoine Maghreb Mediterranée (Alif).
Keywords: Monuments -- Djerba

Djerba : Mobilisation pour la restauration des mosquées Sidi Jmour et Sidi Zayed (2024)
Des travaux urgents devraient être effectués pour la restauration et conservation de deux monuments religieux dans l’île de Djerba, la mosquée Sidi Jmour et celle de Sidi Zayed. La mosquée Sidi Jmour est parmi les 31 sites et monuments contenus dans le dossier d’inscription de l’Ile de Djer…
Keywords: Monuments -- conservation -- Djerba; Sidi Jmur, mosquée (El Groo, Djerba); Sidi Zayid, mosquée (Houmt Souk, Djerba)

Tamazight en Tunisie (2/2) Doucement, tranquillement… sûrement. - Ould Amar, Tahar (tasghunt taseklant, 2024)
Architecture adaptée à l’environnement et aux éventuelles agressions. …Nous Rentrons « chez nous » à Guellala, belle petite ville située au sud de l’Ile et  qui porte bien son  patronyme amazigh : aqellal  (la jarre). Entre deux ateliers de poterie s’insère un…autre atelier de poterie. Au centre de la coquète petite ville s’élève la jarre la plus haute […]
Keywords: Linguistique; Moeurs et coutumes -- Djerba; Récits de voyage -- Djerba

الجزائر في حاجة إلى قيم وثقافة التاجر الميزابي - جابي, ناصر (2024)
كنت مُجبرا وأنا طفل صغير على مغادرة الحي الذي تسكنه العائلة في وسط المدينة ببلوزداد- بلكور – يوميا، للالتحاق بالمتوسطة والثانوية لاحقا، بأعالي العاصمة، وهو ما فرض عليّ استعمال حافلات النقل العمومي، التي تحولت إلى مجال واسع للملاحظة بالنسبة لي، خارج محيط العائلة والحي الضيقين. من جملة الملاحظات التي استرعت انتباهي وأنا صغير صورة الكهل […]
Keywords: Récits de voyage -- Mzab

Ancient Infusen Poems (Part-I) - Buzakhar, Mazigh (Medium, 2024)
from 12th Century Manuscript ‘Siyar Wisyani’: Aẓil, the wise woman
Keywords: Poésie -- Djebel Nefousa

أثر ابن عمر الوارد في الخوارج: نظراتٌ في ثبوت المقالة وتوجيه الدلالة (Maarig, 2024)
عمـر بن أحمـــد بن حمــد الخليلــي   بسم الله الرحمن الرحيم الحمد لله رب العالمين، والصلاة والسلام ع
Keywords: Kharijisme

Réflexions sur l’attentat religieux survenu au sultanat d’Oman - Thouroude, Guillaume (2024)
Comme beaucoup d’entre vous, j’ai été profondément attristé par la nouvelle de l’attentat qui a eu lieu près de la mosquée chiite du quartier Wadi Al-Khabir à Mascate. Ayant vécu …
Keywords: Attentats -- Oman -- 2024

Azzedine Ben Yacoub : "Je revendique mon opportunisme pour la Tunisie" - Trabelsi, Salem (2024)
Mercredi 24 juillet a démarré la cinquième édition du festival du tourisme sportif et culturel, à l'initiative de l'Association «al-Irada pour la
Keywords: Vie culturelle -- Djerba

« S’randi en fête » : le festival Djerbien qui met en scène le tourisme culturel et sportif - Chemli, Abir (2024)
« S’RANDI en fête », c’est sous cet enseigne que l’Association Al Irada pour la culture et le développement à Srandi, délégation de Djerba-Ajim, a choisi de célébrer le cinquième festival du tourisme sportif et culturel. C’est ce qui a été annoncé aujourd’hui, lundi 22 juillet lors d’une conférence de presse tenue à Tunis par...
Keywords: Tourisme -- Djerba

Oman: Partisan Non-Intervention - Barrett, Roby Carol; Sherwood, Leah (E-International Relations, 2024)
While Oman often adopts non-interventionist positions, it is an oversimplification to call it a neutral state.
Keywords: Politique étrangère -- Oman -- 2020-....

De traficante a cativo: resgate e escravatura no Atlântico e Mediterrâneo, séc. XVIII - Daddi Addoun, Yacine; Candido, Mariana P. (2024)
Mariana P. Candido e Yacine Daddi Addoun (Emory University & Center for Research and Studies on Ibadism) | 8 de julho | Sala 3, ICS-ULisboa | apresentam a palestra "De traficante a cativo: resgate e escravatura no Atlântico e Mediterrâneo, séc. XVIII"
Keywords: Esclavage -- Afrique du nord

Les légendes djerbiennes (djerba web, 2010)
Keywords: Croyances populaires -- Djerba; Monuments -- Djerba; Sidi Zakri, mosquée (Mezraya, Djerba)

An Ibadi Tafsir at the British Library | نسخة من تفسير هود الهواري في المكتبة البريطانية - Love Jr, Paul M. (2024)
Last summer, in a series of email exchanges, colleagues Dr. Aurélien Montel (Maître de Conférence, Université Toulouse – Jean Jaurès) , Mr. Soufien Mestaoui (Director, Ibadica), and Dr. Micha…
Keywords: Coran -- Commentaires -- 9e siècle; Hawwārī, Hūd b. Muḥkim al-; Manuscrits -- Londres

Baudin : le prélude à l'affaire Ben Ayed. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Comment la France par ses brouilleries et l'art de la manipulation a t'elle précipitée la chute de Mahmoud Ben Ayed ? La France a jouée un double jeu
Keywords: Famille Bin Ayyad

Sofrat Ben Ayed - سفرة بن عياد - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Sofrat en arabe "سفرة" signifie table ou buffet. Celle de Ben Ayed était grandiose, riche aussi bien en différents mets, qu'en vaisselles et service de tables
Keywords: Famille Bin Ayyad

La mille deuxième nuit d'Orient - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
C’est dans le cadre très oriental d’un des plus anciens palais de Tunis que se déroula la mille et deuxième nuit qui nous avait été offert, le palais Ben Ayed, une demeure séculaire, (construit au XVIII ème siècle par les frères Regeb, Grand Douanier de Tunis et Hmida Ben Ayed, Général et Caïd de l’Aradh) … Continuer la lecture de « La mille deuxième nuit d’Orient »
Keywords: Famille Bin Ayyad

Février 1783: Si Redgeb Ben Ayed est nommé Grand Douanier de Tunis. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Le Bey a disposé de celte place en faveur de Sidi Ben Ayed, qui jouit de la considération publique. Le sieur d'Esparron a rendu visite à ce nouveau
Keywords: Famille Bin Ayyad

Les huileries Ben Ayed à travers le temps - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
De la huilerie souterraine Ben Ayed de la fin du 18 -ème siècle à la huilerie du 20 -ème siècle, les Ben Ayed ont su s'adapter à leur environnement et à la technologie de chaque époque.

Conte populaire tunisien: Les sept petites filles et l'ogresse - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Un conte populaire tunisien exceptionnel de 1960, 15 minutes de pur plaisir réalisé dans les studios de la radio tunisienne, adapté par Pierre Comte, avec : Mohamed Agrabi dans rôle du conteur , Pierre Comte dans le rôle de l’ogresse, Ali Ben Ayed dans le rôle du père , Jamil Joudi dans le rôle du … Continuer la lecture de « Conte populaire tunisien: Les sept petites filles et l’ogresse »
Keywords: Littérature

Le Touring Race Budapest - Constantinople by Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Entre le 29 juin et le 6 juillet 1912, le Royal Automobile Club Hongrois organisait un Touring race sous la présidence du prince Tuniso-turque Rchid Ben Ayed
Keywords: Famille Bin Ayyad

Un Tunisien à la cour du Roi Louis Phillipe de France en 1831 - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
C'est le Général Mohamed Ben Ayed munit des pleins pouvoirs qui sera choisit par Hussein Bey pour le représenter au près du Roi des Français Louis-Phillipe
Keywords: Famille Bin Ayyad

L'indétronable Ali Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Il y a des personnes qui ont marqués l'Histoire de Tunisie et Aly Ben Ayed ( علي بن عياد ) en fait inévitablement parti. Ali Ben Ayed est né le 15 août 1930
Keywords: Théâtre -- Djerba

L'enfer de Djerba sous la seconde guerre mondiale - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
L'Histoire, ne l'oublions jamais, est faite par des êtres de chair et de sang, des femmes et des hommes auxquels nous pouvons nous identifier.
Keywords: Djerba -- 1939-1945

La visite de Lady Herbert chez Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Mme Christina Wood, l'épouse du Consul général britannique, désireuse de nous présenter à l'une des premières familles de Tunisie, qui se nomme Ben Ayed
Keywords: Famille Bin Ayyad

Poème perdus et retrouvés de Ben Moussa El Fetairi - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Les vers de Ben Moussa poète satirique et moraliste jouissaient autrefois d’une renommée considérable dans la Régence de Tunis malheureusement oublié de nos jours. Ahmed Ben Moussa connu sous le nom de Ben Moussa El Fetairi, fabricant de beignets, est originaire de Ghomrassen. D’abord apprenti dans la boutique paternelle puis patron. Il eut tout en … Continuer la lecture de « Poème perdus et retrouvés de Ben Moussa El Fetairi »
Keywords: Poésie

Alexis Gierra: l'un des premiers agents de Hamouda Pacha en France - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Cela m’a beaucoup déplu de ne pas avoir été en sa compagnie ainsi que j’aurai du l’être, et ce fut aussi préjudiciable à mon emploi de consul tunisien
Keywords: Famille Bin Ayyad

Les Djerbi d'Istanbul du 18-éme au 20-éme siècle. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Kacem Ben Ayed, était à la tête d'une délégation chargée de 1748 à 1752 de livrer à l'Empire Ottoman, les offrandes de la Régence notamment les troupeaux de bétails.
Keywords: Emigration -- Djerba -- Turquie; Famille Bin Ayyad

Regeb Bounemra, Hamida Ben Ayed, et Hamouda Lasram chefs miltaires et proches conseillers de Hammouda Pacha - رجب بونمرا ، حميدة بن عياد وحمودة لصرم أحد مستشاري المقربين لحمودة باشا - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Ce Général était l'un des Hommes tunisiens les plus proches de Hamouda Pacha, l'un de ses meilleurs conseillers, Ibn Abi Dhiaf le décrit comme
Keywords: Famille Bin Ayyad

من سيدى يونس العروسي بن عياد الي خير الدين باشا - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
(ابريل 1868)
Keywords: Famille Bin Ayyad

Ibrahim Ben Ayed: l'inventeur du parachute pour avion en 1930 - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Ibrahim Ben Ayed, prince tunisien par l’alliance de la famille Ben Ayed au Vice-roi d’Egypte Mustapha Fazil, et ingénieur en aéronautique, il fut le premier
Keywords: Famille Bin Ayyad

Témoignage: fiançailles chez Ben Ayed au 19-éme. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Celle que je vais avoir le plaisir de te décrire tant bien que mal, vient d'être célébrée dans la famille Ben Ayed, l'une des plus riches et des plus consid
Keywords: Famille Bin Ayyad

قائمة مساجد جزيرة جربه تم ضبطها ميدانيا بين جويلية 2018 و آوت 2019.العمل من انجاز جلال فتح الله. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
قائمة مساجد جزيرة جربه تم ضبطها ميدانيا بين جويلية 2018 و آوت 2019.العمل من انجاز جلال فتح الله.
Keywords: Architecture -- Djerba

Répertoriage et recensement des mosquées de Djerba - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Répertoriage et recensement des mosquées de Djerba
Keywords: Architecture -- Djerba

Le petit labyrinthe du palais Ben Ayed à Djerba - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Keywords: Famille Bin Ayyad

Le Prince Abdallah Ben Ayed m'a dit ... - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Un des résultats de la guerre des persécutions, des mauvais traitements, de la crainte, en un mot, de la malice des hommes, c’est de chasser d’un pays à l’autre, d’un continent à l’autre, un grand nombre de personnages remarquables. C’est ce qui nous vaut, à nous, habitants de la paisible et heureuse Amérique, la rencontre … Continuer la lecture de « Le Prince Abdallah Ben Ayed m’a dit … »
Keywords: Famille Bin Ayyad

Deux Beys de Tunis au Ksar Ben Ayed de Cedriane, Djerba. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
Hussein Bey aura passé une semaine à Djerba en compagnie du Général Ben Ayed qui décèdera une année plus tard.
Keywords: Famille Bin Ayyad

رسالة من القائد حميدة بن عياد إلى نسله - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2021)
بنيا قصر بن عياد بجربة عام 1775 وهاهنا يعدوالتريخ نفسه اليس تحذيراً من القايد حميدة بن عياد الي احفاد
Keywords: Famille Bin Ayyad

Le Palais Ben Ayed de Gammarth - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Le Palais Ben Ayed de Gammarth a été édifié vers 1831, par le Général Mohamed Ben Ayed, envoyé extraordinaire auprès du Roi Louis Philippe de France par le Bey de Tunis Hussein II
Keywords: Famille Bin Ayyad

Tchakchouka by Lesley Blanch - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Sur la petite île de Djerba, qui ressemble à un jouet, au large des côtes du sud de la Tunisie, se trouve une petite ville, Houmt-Souk,
Keywords: Alimentation -- Djerba; Récits de voyage -- Djerba

Carte des Edifices / Terrains Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Cette carte a pour objectif de lister les édifices (et terrains) appartenant ou ayant appartenus à la famille Ben Ayed d'un point de vue historique.
Keywords: Famille Bin Ayyad

Entretien à Londres avec la Princesse Kheyriye - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Il y a environ deux mois avant que je ne quitte Constantinople" dit-elle. "J'ai découvert que tout ce que je faisais était soigneusement espionné, ma maison
Keywords: Famille Bin Ayyad

La caserne husseinite ou Saussier - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
La caserne husseinite appelée aussi caserne d'El Gorjani est situé dans le quartier du même nom. Elle est occupée aujourd'hui par la brigade criminelle. Une
Keywords: Famille Bin Ayyad

La manufacture de draps d'El Battan à Tébourba - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Cette manufacture de draps et d'habillement des troupes a été construite par le Général Mohamed Ben Ayed en 1844 pour diminuer
Keywords: Famille Bin Ayyad

Six images inédites de Djerba en 1873 - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Découvrez six images inédites de Djerba et son histoire. Il s'agit des plus anciennes illustrations pour certains lieux qui date de 1873.
Keywords: Architecture -- Djerba

Inauguration de la Rue Docteur Hassouna Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
En hommage au professeur Hassouna Ben Ayed, une rue de Tunis à Bab Saadoun, prêt de la faculté de médecine dont il fut le doyen portera désormais son nom.
Keywords: Famille Bin Ayyad

La branche princière de la famille Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Mohamed Taher, née à Tunis en 1853 de l'alliance du Général Mahmoud et de la dame Daddou Bent Hamda Djilani, épousera la Princesse Roukia Fazil, fille
Keywords: Famille Bin Ayyad

La fontaine Çengelköy à Istanbul - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Cette fontaine dans l’un des quartiers d’Istanbul a été construite par le Grand Vizir ottoman Youssef Ziyedudinn Pacha en hommage à sa femme décédée, mais quelques années après la mort du Vizir en 1819 l’eau s’arrêta de couler et ne parvenait plus à la fontaine à cause de changement de propriétaire, les habitants et passagers … Continuer la lecture de « La fontaine Çengelköy à Istanbul »
Keywords: Famille Bin Ayyad

Dans un jardin mauresque - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Cette illustration est une vue prise dans le magnifique jardin du Consul – Général britannique à La Marsa, près de Tunis. La maison de campagne, qui est la résidence principale du consul général britannique dans la régence de Tunis, était à l’origine un palais appartenant au Bey, qui l’a cependant offert en présent au gouvernement … Continuer la lecture de « Dans un jardin mauresque »
Keywords: Famille Bin Ayyad

Histoire d'un viking ottoman et d'une princesse révoltée - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
Ali Nouri Bey, suédois converti, ancien Consul général de Turquie à Rotterdam, qui est actuellement à Londres avec sa femme, la Princesse Hairie Ben-Ayad, est l’un des dirigeants éminents du Parti légitimiste turc. Ce Parti revendique et œuvre pour la réinstallation sur le trône de Turquie le Sultan Murad V, qui serait devenu fou quelque … Continuer la lecture de « Histoire d’un viking ottoman et d’une princesse révoltée »
Keywords: Famille Bin Ayyad

L'épidémie de peste à Djerba en 1784 - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2022)
La peste toucha en premier lieu Houmt-Souk, précisément Taourit, puis Ajim, ensuite elle se propagea dans toute l'ile en terminant par les villages de
Keywords: Epidémies -- Djerba -- 1784

Le voyage à Djerba du Baron Heinrich Von Maltzan - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2023)
Le Baron Heinrich Von Maltzan est un célèbre explorateur allemand du 19 éme Siècle, qui a visité la Tunisie et se rend de Sfax à Djerba
Keywords: Récits de voyage -- Djerba

L'armateur corsaire Hamida Ben Ayed et les marins d'Ajim - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2023)
Au mois de Ramadan de l'année 1200 de l'hégire (correspondante à l'année 1786), le gouverneur de Djerba Sidi Hamida Ben Ayed pris un navire Vénitien
Keywords: Famille Bin Ayyad

Reconstruction 3D du Ksar Ben Ayed - Episode 1 - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2024)
La reconstruction 3D a posé un défi de taille, nécessitant l'utilisation d'une tablette graphique pour travailler minutieusement chaque détail à la main
Keywords: Monuments -- Djerba

In Tunisia, Opening a World of Opportunities for Girls (JDC, 2021)
For the past 14 years, the JDC-supported Kanfei Yonah school in Djerba, Tunisia, has given young girls and women access to education.
Keywords: Enseignement -- Djerba; Judaïsme -- Djerba

Each egg, a wish on the Jewish pilgrimage to the strange Tunisian synagogue - Israel, Noticias Aurora; Abel, Pablo (2022)
Each egg, a wish on the Jewish pilgrimage to the strange Tunisian synagogue
Keywords: Judaïsme -- Djerba

Le mythe de la malédiction de Cham et la côte swahili - Belhacel, Abdelhakim (2024)
Keywords: Esclavage -- Zanzibar

Sami Ben Tahar, Activités: Site de Henchir Bourgou (Jerba) - Dabbaghi, Ali (Institut national du patrimoine, 2023)
Sami Ben Tahar, Chercheur archéologue à l'INP Site de Henchir Bourgou (Jerba), une fouille extensive Dans le cadre des activités scientifiques de l’INP une fouille extensive a été menée sur le site de Henchir Bourgou (Jerba) au cœur de l’agglomération urbaine antique au courant des mois de juin et juillet 2023. Elle a livré des une fouille extensive a été menée sur le site de Henchir Bourgou (Jerba) au cœur de l’agglomération urbaine antique au courant des mois de juin et juillet 2023. Elle a livré des vestiges afférents à une grande maison construite à l’époque augustéenne, réaménagée à l’époque flavienne et complètement abandonnée vers la fin du IIe s. ou au tout début du IIIe s. ap. J.-C.
Keywords: Archéologie -- Djerba

Interviewing Religion – A Chat With Adam Gaiser - Gaiser, Adam R.; Floden, Tuve (TuveofLoden, 2023)
Dr. Gaiser discusses his research on Ibadi Muslims and early Muslim sectarianism, and suggests books for further reading.

Libye. L’Agence de sûreté intérieure doit cesser de piétiner les droits humains au nom de la «préservation de la vertu» - Amnesty International (2024)
Les autorités libyennes doivent assurer la libération immédiate de toutes les personnes détenues uniquement pour avoir exercé leurs droits fondamentaux.
Keywords: Vie politique -- Libye -- 2011-....

Watch.. The Mufti of the Sultanate of Oman listens to Abu Ubaida’s speech (Tellerreport, 2024)
Keywords: Vie politique -- Oman -- 2020-....

The jurisprudential corpus and the history of Ibadism in medieval Libya: additions and difficulties / استغلال المدوّنة الفقهيّة الإباضيّة في دراسة تاريخ ليبيا الوسيط بين الإضافات والصعوبات: كتاب اللقط نموذجا - Khlifi, Houcine (LibMed, 2024)
Houcine KHLIFI (University of Sousse, Tunisia) Introduction This study questions the relations between fiqh and history through the lense of Kitāb al-Luqaṭ by al-Šammāḫī. According to al-Warǧilānī, the imam Abū l-Ḫaṭṭāb established the first Ibāḍī emirate near Tripoli (in Ṣayyād) in 140/757. Later, in the...
Keywords: Fiqh -- Libye -- 8e siècle

وفاة محمد شفيق قوجة، الباحث و أستاذ التعليم العالي (أنباء تونس, 2024)
تنعى وزارة الشؤون الثقافية، بكلّ حسرة وأسى، أستاذ التعليم العالي محمد شفيق قوجة الذي وافاه الأجل المحتوم اليوم الخميس 11 جانفي 2024 بعد صراع مع المرض. وقد شغل الرّاحل خطّة مدير مخبر البحوث في الفنون والموسيقى والتراث والمحيط والمجتمع بالمعهد العالي للفنون والحرف بقابس، كما ترأّس محمد شفيق قوجة سابقا جمعية صيانة جربة. وبهذه المناسبة الأليمة تتقدم وزارة الشؤون الثقافية بأحرّ التعازي إلى عائلة الأكاديمي الرّاحل محمد شفيق قوجة وإلى الأسرة الفكرية والثقافية الموسعة، راجية من الله تعالى أن يتغمّد الفقيد برحمته الواسعة وأن يلهم أهله وذويه جميل الصبر والسلوان. وإنا لله وإنا إليه راجعون.
Keywords: Biographies

Oman, médiateur du Golfe ? Caractéristiques d’une diplomatie singulière - Clément, Justine (Les clés du Moyen-Orient, 2023)
Keywords: Politique étrangère -- Oman -- 2020-....

Tunisie : La longue marche de Djerba vers le gouvernorat - Mahroug, Moncef (Nawaat, 2023)
Cela fait près d’un demi-siècle que les Djerbiens veulent que leur île devienne un gouvernorat. En 2021, le gouvernement s’est engagé à commencer à étudier leur demande. Trois ans plus tard, cet engagement n’a toujours pas été tenu. Mais cela n’entame en rien la détermination des insulaires.
Keywords: Vie politique -- Djerba -- 2011-....

Thinking about Muslim Sects and Schools - Gaiser, Adam R. (Fifteen Eighty Four: Academic perspectives from Cambridge University Press, 2022)
The Muslim community, known as the umma, is meant to be united. The Qur’an, in chapter 29, verse 92, states that ““Indeed, this your umma is one umma, and I am your Lord; so worship Me.” Yet Muslims, just like Jews, Christians and other religious groups, divided into various communal divisions quite early in their history.

Ibadism and Oman’s stance of ‘active neutralisation’ (Arab Digest, 2020)
Summary: We are pleased to publish Grace Dunn's winning entry in the inaugural Arab Digest - Anglo-Omani  Society Essay Competition for Year 12 and Year 13 students (ages 16 -18).

Could Libya Become Africa’s Afghanistan? - Hasse, Khalil El (Fikra Forum, 2023)

Documenting Pluralistic Cultural Heritage in Djerba, Tunisia - Tlili, Safouane (American Society of Overseas Research (ASOR), 2023)
ASOR's implementing partners highlight the importance of pluralistic heritage through documentation projects
Keywords: Monuments -- conservation -- Djerba

Ghardaïa : un puissant hommage au théologien Cheikh Mohamed Ayoub Sedki - Nahnah, Ahmet (Dzair Scoop, 2023)
Un puissant hommage a été rendu, dans la soirée de vendredi à samedi, à Beni Izguen (Ghardaïa), au théologien Cheikh Mohamed Ayoub Sedki, qui a consacré sa vie au service de l’Islam en tant qu’auteur de l’exégèse orale des versets de la Sainte Coran. et des sermons hebdomadaires pendant plus de quarante ans. Une cérémonie […]

Legal and Theological Dimensions of Slavery in an Early Ibāḍī Text - Anchassi, Omar (Trasis (Trajectories of Slavery in Islamicate Societies), 2023)
Keywords: Esclavage -- Oman

Dans la vallée du M’Zab, Ghardaïa la Pentapole - Heim, Jean-Pierre (Chroniques d‘architecture, 2023)
A Ghardaïa, dans le dédale des rues, les murs sans fenêtres laissent parfois apparaître un moucharabieh qui donne à voir la mosquée.
Keywords: Architecture -- Mzab

Tunisie : Journées internationales du patrimoine de Djerba - kapitalis, webmaster (Kapitalis, 2022)
Djerba Cult, les Journées internationales du patrimoine de Djerba, se tiendront du 16 au 18 mai 2022n en marge du pèlerinage de Ghriba.
Keywords: Monuments -- conservation -- Djerba

The History Of Nafousa Mountains' Jews - Altaeb, Malak (2020)
Not a single Jew remains in Libya today but their history remains alive. Many of those who once lived home, are scattered all over the world, with stories to tell to their grandchildren. I am sure stories worth telling! Once upon a time, Jews and Muslims lived together in Libya embracing their differences and living in harmony. It is important to know that Jews lived in many parts around Libya, not only in major cities. Indeed, the fact that Libya was an Italian colony and did not fall under the Vichy regime in France made the fate of the Jews of Libya different from that of the Jews of Algeria, Morocco and Tunisia.   I embarked on the journey to find answers about the once who lived home, it is something we cannot simply erase. This dates back to 2016 when I started the process of questioning and though it has only been four years, but I know for fact, I still have a long way to go. However, I managed to get to know Libyan Jews and talk to them and know their families’ stories.   I always try to picture how life was for them in Libya. When I read […]
Keywords: Judaïsme -- Djebel Nefousa

Djerba, une île qui fait toujours rêver ! - Ladjimi, Mohamed Habib (Webdo, 2021)
Une récente escapade sur l’île de Djerba nous a redonné un peu de baume au cœur dans la mesure où il existe, encore en Tunisie, un petit coin de paradis qui a conservé l’arôme d’un « bon vieux temps » révolu dans les villes du continent. Reportage : Lundi 22 mars 2021, il est 18h00. […]
Keywords: Tourisme -- Djerba

Marianne Catzaras au « Violon Bleu » : L’impossible voyage - Hamza, Alya (La Presse de Tunisie, 2021)
Marianne est femme de l’entre-deux : entre deux mers, entre deux ports, entre deux pays, entre deux langues. On pourrait continuer longtemps à essayer de
Keywords: Arts -- Djerba

Des tortues marines découvertes mortes sur la plage de Ras el Rmal à Djerba - Khdimallah, Meriem (La Presse de Tunisie, 2021)
Afin de tirer la sonnette d’alarme sur la pollution marine, Talel Lassoued, président de l’agence de voyage ‘’Randonnée club Tunisie’’ et représentant
Keywords: Crises environnementales -- Djerba

Décès de Béchir Ben Yahmed : la Tunisie, orpheline de « Si Béchir » - Dahmani, Frida (Jeune Afrique (site web), 2021)
Plus jeune ministre de Habib Bourguiba, BBY a contribué aux pourparlers pour l'indépendance de la Tunisie. Devenu patron de presse, ce natif de Djerba continuait à accorder une place spéciale à son pays d'origine dans « Jeune Afrique ». Témoignages. – Jeune Afrique
Keywords: Journalisme -- Djerba

Djerba : L'énigme du Palais Ben Ayed, cet autre immeuble menaçant ruine - Bourial, Hatem (Webdo, 2019)
Le paysage djerbien a profondément changé ces dernières décennies. Sans évoquer ici le bétonnage de toutes les plages qui se trouvent à l’est de l’île, il convient aussi de souligner l’architecture peu appropriée de nombreuses villas qui se trouvent disséminées autour des bourgs de Djerba. Ce changement du paysage et cette rupture avec les équilibres […]
Keywords: Monuments -- conservation -- Djerba

Quand un Djerbien tire la sonnette d’alarme : Djerba se meurt, lentement et dans l’indifférence totale - Jeriri, Lotfi (tuniscope.com, 2018)
Lotfi Jeriri est journaliste mais il est surtout un Djerbien qui s’inquiète pour son île et qui voudrait voir les hôteliers faire preuve de plus de créativité de prise d’initiative pour sortir l’île de sa torpeur. Voici ce qu’il a écrit :
Keywords: Crises environnementales -- Djerba

La petite histoire de l'aéroport de Djerba ou comment construire quand manque la pierre... - Bourial, Hatem (Webdo, 2016)
Lors de la construction de l’aéroport de Djerba, les ingénieurs en charge des travaux ont eu à faire face à un problème en apparence insoluble. En effet, selon toute évidence et à cause du relief plat et sans hauteurs notables de l’île, la pierre allait manquer pour construire les pistes. A l’époque, durant les années […]
Keywords: Aéroport -- Djerba

Oman et les pérégrinations des textes ibadites (fin XIXe-début XXe s.). - Andriyanova, Olga (Le Carreau de la BULAC, 2016)
Autour d’une exposition d'ouvrages patrimoniaux ibadites à la BULAC
Keywords: Manuscrits -- Oman

Tunisia’s Diverse Djerba Island and Its Annual Jewish Pilgrimage - Pereltsvaig, Asya (Languages Of The World, 2015)
[This post was originally published in June 2012] An earlier post discussed Ibadi Islam, the predominant faith in Oman. In addition to Oman and its settlements in East Africa, the Ibadi faith can also be found in small pockets in North Africa. One notable center of Ibadi Islam is Djerba, an island in the Gulf […]
Keywords: Judaïsme -- Djerba

Ibadisme et conflit (Islam) - Gil (Le conflit, 2013)
L'ibadisme, troisième branche de l'Islam, après le sunnisme et le chiisme, qui ne possède plus comme aire d'influence significative que l'Émirat d'Oman, est l'héritier (même si cet héritage est plutôt considéré aujourd'hui d'une manière négative) du khâridjisme...

Résumé de la soutenance d’Ahmad al-Ismaili par Moez Dridi - Dridi, Moez (Islams ibadites, 2012)
Compte rendu de la thèse “La théologie ibadite omanaise du Ie/VIIe siècle au VIIe/XIIIe siècle” (École Pratique des Hautes Études, Paris) soutenue publiquement par monsieur Ahmed al-Ismaili le 17 avril 2012. Cette thèse sur la théologie ibadite, soutenue par Ahmed al-Ismaili à l’École pratique des hautes études est singulière par plusieurs aspects. Pour la première … Continuer la lecture de Résumé de la soutenance d’Ahmad al-Ismaili par Moez Dridi →

Adel Besrour : « Menzel Feneguia » témoigne de ce que furent les Menzels typiques de l’île de Djerba - Djait, Amel; Besrour, Adel (1001 Tunisie, 2011)
Une aventure que les héritiers affrontent avec passion mais non sans difficultés. Ouverture attendue pour le mois...
Keywords: Monuments -- conservation -- Djerba

Life in Israel: The Jews of Djerba - G., Rafi (Life in Israel, 2011)
Keywords: Judaïsme -- Djerba

Djerba: Ouverture de la Bibliothèque Lina-Ben-Mhenni (La Presse de Tunisie, 2021)
Le 17 octobre a été inaugurée à Mezraya, dans la campagne djerbienne, la Bibliothèque Lina-Ben- Mhenni. Le premier établissement d’une série de
Keywords: Vie culturelle -- Djerba

بالصور: تفاصيل من زيارة السلطان تيمور بن فيصل إلى بريطانيا عام 1928 (صحيفة أثير الإلكترونية, 2021)
أثير- تاريخ عمانإعداد: د. محمد بن حمد العريميقام السلطان تيمور بن فيصل برفقة مستشاره المالي بروترام توماس بز
Keywords: Relations -- Oman -- Royaume-Uni

Kaïs Saïed veut que Djerba devienne un patrimoine de l'UNESCO (Réalités Online, 2021)
C’est ce lundi 7 juin 201é que le président de la République, Kaïs Saïed, a reçu Audrey Azoulay, Directrice générale de l’UNESCO, au Palais de Carthage. Celle-ci, pour rappel, s’est rendue en Tunisie dans le cadre de sa participation à la 8ème édition de la conférence sur le patrimoine maritime. Pour Kaïs Saïd, c’était l’occasion […]
Keywords: Monuments -- conservation -- Djerba

Le fondateur de Jeune Afrique Béchir Ben Yahmed succombe au covid-19 (Réalités Online, 2021)
Le journaliste franco-tunisien et fondateur du groupe panafricain Jeune Afrique, Béchir Ben Yahmed, est décédé dans la soirée du dimanche 2 mai 2021 soit la veille de la célébration de la journée mondiale de la liberté de la presse. Âgé de 93 ans, le défunt a succombé au nouveau coronavirus Covid-19. Fils d’un commerçant de […]
Keywords: Covid-19 -- Djerba

توفي قبل نحو 97 عامًا: السيد خالد بن برغش وجزيرة المنفى (سانت هيلانة) - الجهورية, أحلام بنت حمود (صحيفة أثير الإلكترونية, 2021)
المنفى أدبيا يختزل ثيمة الاستبعاد والخروج والهجرة القسرية والغربة والفراق، والنفي كحدث تاريخي يختزل في داخله فترة تاريخية بشخوصها وظروفها المختلف…
Keywords: Biographies -- Zanzibar

قبل 77 عامًا: تفاصيل زيارة قام بها السلطان سعيد بن تيمور إلى مصر وفلسطين (صحيفة أثير الإلكترونية, 2021)
أثير- تاريخ عمان إعداد: د. محمد بن حمد العريميحرص العديد من سلاطين أسرة البوسعيد في مسقط وزنجبار وبالأخص منذ

Tunisie : Interruption des traversées du Bac de Djerba Ajim - aroua (Directinfo, 2021)
Vendredi matin, le bac de Djerba Ajim a interrompu ses traversées dans les deux sens en raison de vents violents, selon une source officielle responsable des traversées du bac de Djerba, rapporte Shems Fm.
Keywords: Barques -- Djerba

Environnement : Le schéma directeur d’aménagement de la zone sensible de Djerba présenté à un conseil ministériel - Bessais, Raja (Webmanagercenter, 2021)
L’étude relative au Schéma directeur d’aménagement de la zone sensible de l’île de Djerba sera bientôt soumise à un conseil ministériel, afin de l’adopter et d’entamer l’élaboration d’un pacte de développement durable et d’un plan climatique englobant les projets envisagés pour…
Keywords: Urbanisme -- Djerba

تعرف على المستشار السياسي لسلطان زنجبار - المحذوري, سليمان بن عمير (صحيفة أثير الإلكترونية, 2021)
مسقط-أثير  إعداد: د.سليمان المحذوري من خلال مراجعتي لكتاب جهينة الأخبار في تاريخ زنجبار لفت انتباهي اسم الشيخ هلال بن عامر الحارثي؛ إحدى الشخصيات العُمانية التي كان لها حضور سياسي بارز في زمن سلطان…
Keywords: Vie politique -- Zanzibar -- 1888-1890

Tunisie-Culture numérique : “Djerba View” un nouveau projet culturel 3D [Audio] - TN24.TN - Ben Slimane, Rania (2021)
La jeune Emna Ben Jeddi, originaire de l'île de Djerba du gouvernorat de Médenine a réussi à lancer un projet culturel numérique intitulé «Djerba View», à travers lequel elle valorise le monument historique la Tour de Ghazi Mustapha grâce à une technique tridimensionnelle qui plonge le visiteur dans l'année 1560, date du déclenchement d'une bataille entre les Ottomans et les Espagnols. Dans une déclaration à la correspondante de Tunisie numérique dans la région, la chef du projet, basée dans
Keywords: Ghazi Mustafa, Burj (Houmt-Souk, Djerba)

L’ultime hommage à Naccache - Ben Nessir, Chokri (La Presse de Tunisie, 2020)
Les hommages posthumes  qui ont suivi le décès de l’écrivain et activiste politique de gauche Gilbert Naccache, dont celui du Président de la République,

Le palais Ben Ayed d'Epinay-sur-Seine - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Le château devient ensuite la propriété notamment de Jean-Baptiste de Sommariva, du général tunisien Mahmoud Ben Ayed ou encore de Don François d’Assise,roi
Keywords: Famille Bin Ayyad

Un duel à l'épée pour le prince Ben Ayed. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Le prince Ben Ayed ayant adressé des paroles injurieuses à M de Latorre, celui-ci chargea deux de ses amis, M. Maurice Leudet
Keywords: Famille Bin Ayyad

Sir Wemyss Reid chez le général Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
J'avais rencontré chez M. Reade (Consul Général) un gentleman tunisien d'une noble et richissime famille, le Général Ben Ayed. Ce gentlemen est juste
Keywords: Famille Bin Ayyad

Sir Grenville Temple rend visite à Ben Ayed en 1834. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Sir Grenville Temple. Sir Grenville Temple 10th est né le 20 juillet 1799, fils de Grenville Temple 9th (1768-1829). Pendant un certain nombre d’années, il fut officier dans le 15-ème régiment des hussards. Le 12 décembre 1826, il fut mis à la demi-solde dans l’armée. En février 1829, il succédera à son père et deviendra … Continuer la lecture de « Sir Grenville Temple rend visite à Ben Ayed en 1834. »
Keywords: Famille Bin Ayyad

Ben Ayed organisateur de la première exposition tunisienne à la Great Exhibition de Londres en 1851. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Le Général Mahmoud Ben Ayed, sera chargé par Ahmed Pacha Bey d'organiser cet événement pour la Tunisie, il sera nommé haut commissaire pour cette mission
Keywords: Famille Bin Ayyad

Etude des céramiques du Ksar Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
« Parmi les pièces anciennes les plus importantes que nous a léguées Ie passé de Djerba, il faut mentionner en premier lieu le magnifique ensemble de revêtements céramiques du Palais des Ben Ayed. Ce palais, ou plutôt cette succession de palais, est bâti à un kilomètre environ au nord de Mahboubine, à la limite des … Continuer la lecture de « Etude des céramiques du Ksar Ben Ayed »
Keywords: Famille Bin Ayyad

La mosquée Hadherbach - جامع حاضر باش - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
La mosquée Hadher Bach est situé à un kilomètre de Midoun, sur la route de Mahboubine. On raconte à tort que cette mosquée a été édifiée par Mahmoud Ben Ayed.
Keywords: Famille Bin Ayyad

Kobèt El khyèl du mausolée Sidi Zitouni - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Ce monument a été édifié à la fin du XVIIIème siècle par Hmida Ben Ayed, alors gouverneur, Guèyed (Caïd), de l’île de Djerba
Keywords: Famille Bin Ayyad

Farhat Ben Ayed : un délégué tunisien du Destour à Paris en 1920 - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Les amitiés que Farhat Ben Ayed a nouées dans les milieux politiques parisiens lui permettent de faire revenir le problème tunisien à la Chambre des députés.
Keywords: Famille Bin Ayyad

Mosquée du Caïd Hmida Ben Ayed (جامع القايد حميدة بن عياد) - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Le caïd et Général Hmida Ben Kassem Ben Ayed a édifié cette mosquée ou plus précisément cette école ou « Médersa » en 1785 à Cedghiane Djerba non loin de son palais. Cette grande mosquée se compose de neuf grande chambres qui accueillaient les élèves étrangers non résidents de l’île de Djerba. Le cheikh Kassem … Continuer la lecture de « Mosquée du Caïd Hmida Ben Ayed (جامع القايد حميدة بن عياد) »
Keywords: Famille Bin Ayyad

Hommage au professeur Farhat Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Depuis trente-cinq ans maintenant le professeur Farhat Ben Ayed à la tête de l’ATCC continu sa lutte contre le mal du siècle
Keywords: Famille Bin Ayyad

L'ancienne minoterie Ben Ayed (1880) - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Sous la direction de M. Valensi, ingénieur E. C . P, avait été construite, en 1880, la belle minoterie de Djedeïda, pour le compte de Ben Ayed. Le matériel de la minoterie avait été fourni par la maison Brault et Cie, de Chartres en France. Une turbine hydraulique, actionnée par la Medjerda, faisait mouvoir tout … Continuer la lecture de « L’ancienne minoterie Ben Ayed (1880) »
Keywords: Famille Bin Ayyad

Le poème de la Borda - قصيدة البردة - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Nous retrouvons un extrait de ce poème plus précisément trois vers sur l'un des plafonds du palais Ben Ayed de Djerba à Cedghiane achevée en 1775
Keywords: Famille Bin Ayyad

La vallée industrielle d'El Battan - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Au XIX e siècle est installé sur le pont de la Medjerda (El battan) une manufacture pour confectionner les uniformes de l'armée beylicale, les ouvriers
Keywords: Famille Bin Ayyad

Conte populaire tunisien: Une malice de Jeha - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
On vous propose de découvrir ce magnifique conte populaire tunisien : Une malice de Jeha de 1960.
Keywords: Famille Bin Ayyad

A toi ! petit historien du dimanche ! - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
A toutes ces mauvaises langues, à ses pseudo-historiens du dimanche qui ne prennent même pas le temps de lire un bouquin ou de simplement vérifier
Keywords: Famille Bin Ayyad

Le chebec Tunisien et la course maritime au XVIII siècle - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Le Chebec ou chebek, bateau favori des corsaires. C’était ce type bateau que les Ben Ayed notamment armait pour la guerre de course.
Keywords: Famille Bin Ayyad

Communiqué de l'ASPB - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Le jeudi 29 octobre a eu lieu à Paris, une première réunion de travail entre l'association de sauvegarde du palais Ben Ayed
Keywords: Famille Bin Ayyad

1794: les tripolitains attaquent Djerba - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
En l'an 1794, dans la nuit du lundi au mardi 27 septembre, neuf vaisseaux chargés d'un millier de soldats et commandés par Kara Mohammed arrivèrent de
Keywords: Famille Bin Ayyad

Du Borj Ben Ayed de Gammarth à Marseille - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
On dit que c'est à son retour de mission en France (1831) auprès du Roi Louis-Phillipe que Sidi Mohamed ben Ayed aurait entrepris, au sommet du Cap Carthage
Keywords: Famille Bin Ayyad

Ali Ben Ayed dit Hader Bach - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Hader Bach ! je suis prêt ! répliqua Hadj Ali Ben Ayed, et il versa immédiatement l'énorme somme nécessaire pour délivrer le pays du poids de cette
Keywords: Famille Bin Ayyad

Quelques lettres de notre passé - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Nous présentons ci-dessous, quelques unes des lettres écrites ou citant diverses personnes du clan Ben Ayed, dont les Caids Hmida, Mohamed ben ayed, prince
Keywords: Famille Bin Ayyad

Napoléon III, Mahmoud Ben Ayed et une délégation tunisienne à Paris - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Mahmoud Ben Ayed organise très souvent de somptueux diners dans sa prestigieuse résidence parisienne, dans les notes du capitaine Mourad nous apprenons que
Keywords: Famille Bin Ayyad

La reine Victoria, Lord Palmerston, Sir Thomas Reade et Sidi Mohamed Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Depuis les années 1840, la famille Ben Ayed était une alliée stratégique de la couronne britannique. Le clan Ben Ayed était protégés britanniques
Keywords: Famille Bin Ayyad

Arbre généalogique simplifié de la famille Ben Ayed de 1700 à nos jours - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Après quelques années de recherche, nous avons réussi à reconstituer l'arbre généalogique de la branche tuniso-djerbienne des Ben Ayed de 1700 à nos jours.
Keywords: Famille Bin Ayyad

Une autre version de l'affaire Mahmoud Ben ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Ben ayed réussi, grâce à l’héritage familial et aux différentes charges qu’il occupait à se hisser au sommet des responsabilités de l'Etat et à devenir le fermier général
Keywords: Famille Bin Ayyad

جناب السيد جمشيد يصل السلطنة (صحيفة أثير الإلكترونية, 2020)
أثير- سيف المعوليأكدت معلومات لـ "أثير" وصول جناب السيد جمشيد بن عبدالله آل سعيد (آخر سلاطين دولة البوسعيد في

La princesse Khayriya Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
La princesse Khayriya Ben Ayed est née à Istanbul en 1873, son père n’est autre que le général Tunisien Mahmoud Ben Ayed qui a servi l’Etat Tunisien
Keywords: Famille Bin Ayyad

Le prince Adel Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Le prince Adel Ben Ayed est née dans le quartier de Uskudar à Constantinople en Turquie, en 1883. Il est apparenté, par sa mère la princesse Roukia Fazil Ibrahim
Keywords: Famille Bin Ayyad

جناب السيد جمشيد بن عبدالله سيأتي للسلطنة (صحيفة أثير الإلكترونية, 2020)
أثير- سيف المعولي تداول مواطنون عبر وسائل التواصل الاجتماعي منذ أمس الثلاثاء معلومات تُشير إلى مجيء جناب السيد جمشيد بن عبدالله آل سعيد (آخر سلاطين دولة البوسعيد في زنجبار)، للسلطنة للعيش على أرضها…

Djerba : Projet de restauration de l'église St Joseph de Houmt Souk (Photos) (Almourassel, 2020)
Longtemps fermée, l’église de Houmt Souk à Djerba a réouvert ses portes pour le culte catholique au tournant du nouveau
Keywords: Christianisme -- Djerba

خان بهادر: التاجر العُماني الذي يُضرَب به المثل في الثراء والغنى والعمل الخيري 2/ 3 (صحيفة أثير الإلكترونية, 2020)
مسقط-أثير إعداد: د. محمد بن حمد العريمي ظهر في نهاية القرن التاسع عشر والنصف الأول من القرن العشرين عددٌ من الشخصيات العمانية التي لعبت دورًا مهمًا في مجالات السياسة والتجارة، والتي كانت شاهدة، بل …

Et pourquoi pas un nouveau petit théâtre en plein air à Djerba, Cedghiane ? - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
création de ce nouveau théâtre en plein air,un lieu de vie, accueillant rencontres, concerts, expositions ou la création d’événements divers.
Keywords: Famille Bin Ayyad

Hommage au Professeur Hassouna Ben Ayed - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Biographie du Pr. Hassouna BEN AYED : 1926 – 2010 Né le 21 juillet 1926 à Jerba Etudes primaires à l’école franco arabe de Mahboubine Etudes secondaires à Houmt Souk puis à Tunis (Lycée Alaoui, Lycée Carnot) Etudes médicales en France à la Faculté de Médecine de Paris 1957 – Interne des Hôpitaux Paris Titres … Continuer la lecture de « Hommage au Professeur Hassouna Ben Ayed »
Keywords: Famille Bin Ayyad

La princesse Ben-Ayed : sa folle histoire d'amour. - Ben Ayed, Kais (Palais BEN AYED à Djerba, 2020)
Il y avait à peu près six mois qu’une femme, qui n’avait pas de rivale en beauté, était arrivée à Paris, où son entrée dans le monde avait fait sensation; on s’accordait à dire qu’elle possédait une immense fortune, et l’on savait qu’elle n’était venue à Paris que pour visiter ce que la capitale renfermait … Continuer la lecture de « La princesse Ben-Ayed : sa folle histoire d’amour. »
Keywords: Famille Bin Ayyad

أبدى فيه رأيه بـ”الاتحاد العربي”: حوار مع السلطان سعيد بن تيمور عام 1944 (صحيفة أثير الإلكترونية, 2020)
مسقط-أثيرترجمة: فيصل محمد أمين المنذريفي 21 أبريل 1944م أجرت مجلة المصور المصرية مقابلة صحفية مع السلطان سعيد

بالصور: التاجر العُماني الذي بنى “مسافر خانه” وأوقف له أكثر من 10 عقارات (صحيفة أثير الإلكترونية, 2020)
أثير- تاريخ عمان  إعداد: د. محمد بن حمد العريمي برز في عُمان على مدى تاريخها الطويل العديد من الشخصيات التي أسهمت في صنع هذا التاريخ من مختلف جوانبه المتعددة، فظهر لدينا العلماء، ورجال السياسة، وال…

محمد المرجبي يدخل عالم “تويتر” بـ “الروزنامة العمانية” (صحيفة أثير الإلكترونية, 2019)
أثير-سيف المعوليسيكون متابعو "تويتر" على موعد مع الأخبار العمانية الشائقة والماتعة بدءًا من غد الأربعاء 1 ين

Prolifération du crabe bleu à Djerba: Quand une menace se transforme en opportunité (Webmanagercenter, 2019)
Radhia, Yezza, Samia et plus de 100 autres femmes de la ville d’Ajim, au sud-ouest de l’île de Djerba, vivent au rythme de la mer. Elles gagnent leur vie en travaillant dans la pêche et les activités annexes. Durant plusieurs années, d’octobre jusqu’au mois de mai de chaque année, ces femmes se…

وثائق في الأرشيف تكشف جوانب من علاقات عُمان بالدولة العثمانية (صحيفة أثير الإلكترونية, 2019)
أثير- تاريخ عمان إعداد: د. محمد بن حمد العريمي تُعدّ عُمان عبر تاريخها الطويل أحد أهم الدولالتي كان لها علاقات وتفاعل حضاري مع مختلفالدول والحضارات، وذلك بحكم انفتاحها علىالعالم منذ العصور القديمة …

الإعلان عن اكتشاف أثري جديد في صور (صحيفة أثير الإلكترونية, 2019)
العمانية - أثيرتمكنت وزارة التراث والثقافة بالتعاون مع بعثة من معهد السهول والصحراء الفرنسي من الكشف عن أثر
Keywords: Archéologie -- Oman

أسستها عائلة عمانية: “خزانة العودي” تضم مخطوطات قديمة (صحيفة أثير الإلكترونية, 2019)
أثير - د.محمد بن حمد العريميحرصت العديد من البيوتات والأسر العمانية الكريمة في جناحي القطر العماني (عمان وشرق
Keywords: Bibliothèques -- Oman

أشهر رجال الإمبراطورية العُمانية في ترسيخ السيادة السلطانية: وزراء وقضاة وعسكريون في عهد السيد سعيد بن سلطان (صحيفة أثير الإلكترونية, 2018)
أثير – تاريخ عمان إعداد: نصر البوسعيدي   لكل دولة عظيمة رجال ذوو بأس بالحكمة والإخلاص شديد، فما بالكم ونحن نتحدث هنا عن أشهر رجال الإمبراطورية العمانية الذين كانوا السند الأقوى للسيد سع…

شخصيات حكمت عمان: الشخصية الخامسة والعشرين: السلطان ثُوَيني بن سعيد بن سلطان البوسعيدي (صحيفة أثير الإلكترونية, 2018)
مسقط – أثير تدرّب على شؤون الحُكم في حياة أبيه السيد سعيد بن سلطان إذ كان ينوب عنه في حُكْمِ مسقط أثناء وجود السلطان سعيد في زنجبار؛ منذ عام 1833م. حكم السلطان ثويني من 1856 إلى  1866م، وذلك …
Keywords: Vie politique -- Oman -- 1856-1866

السلطان برغش والخديوي إسماعيل من الصداقة والوئام إلى العداوة والخصام! (صحيفة أثير الإلكترونية, 2017)
أثير – تاريخ عمان إعداد: نصر البوسعيدي     السلطان العماني برغش بن سعيد بن سلطان البوسعيدي، الشاب الطموح الذي حكم زنجبار في عام 1870م، بعد وفاة شقيقه السيد ماجد، كان يملك علاقات حسن الجو…

تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م -الجزء السابع- (صحيفة أثير الإلكترونية, 2017)
أثير – تاريخ عمان إعداد: نصر البوسعيدي نواصل سرد تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م من خلال هذا الجزء السابع: في حضور سعادة السلطان مأدبة لجنة فيشمنجر لا يخفى على من …
Keywords: Relations -- Oman -- Royaume-Uni

الجزء السادس من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2017)
أثير – تاريخ عمانإعداد: نصر البوسعيديذكرنا في ختام الجزء الخامس لرحلة أول سلطان عربي في التاريخ تطأ قدمه
Keywords: Relations -- Oman -- Royaume-Uni

تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م -الجزء الخامس- (صحيفة أثير الإلكترونية, 2017)
أثير – تاريخ عمان إعداد: نصر البوسعيدي انتهينا في الجزء الرابع من رحلة السلطان برغش إلى إنجلترا في زيارته الأخيرة لابن عم الملكة فيكتوريا الدوق (أف كمبيرج) الذي أكرم السلطان أحسن إكرام لينصرف بعده …
Keywords: Relations -- Oman -- Royaume-Uni

تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م -الجزء الرابع- (صحيفة أثير الإلكترونية, 2017)
أثير – تاريخ عمانإعداد: نصر البوسعيديبعدما اختتمنا الجزء الثالث من رحلة السيد برغش إلى إنجلترا، وتحديدا
Keywords: Relations -- Oman -- Royaume-Uni

تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م -الجزء الثالث (صحيفة أثير الإلكترونية, 2017)
أثير – تاريخ عمان: إعداد: نصر البوسعيدي يتذكر القارئ العزيز نهاية الجزء الثاني من رحلة السلطان برغش إلى لندن والذي اختتمناه بلقاء الصحافة البريطانية بالسلطان، وتحديدا مع جريدة الديلي تلغراف والذي أ…
Keywords: Relations -- Oman -- Royaume-Uni

رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م – الجزء الثاني- (صحيفة أثير الإلكترونية, 2017)
أثير – تاريخ عمانإعداد: نصر البوسعيدي في الجزء الأول من تفاصيل رحلة السلطان برغش أول حاكم عربي يصل بزيارة
Keywords: Relations -- Oman -- Royaume-Uni

تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا (صحيفة أثير الإلكترونية, 2017)
أثير – تاريخ عمان إعداد: نصر البوسعيدي (1) يدوّن التاريخ في صفحاته بأن العمانيين، وحكّامهم يعتبرون من أوائل العرب الذين شكلوا وفودا رسمية دبلوماسية لزيارة أوروبا، وأمريكا، تلك الدول التي انطلقت منه…
Keywords: Relations -- Oman -- Royaume-Uni

تعرّف على 20 وثيقة من المعرض المصاحب لمؤتمر علاقات عمان بدول القرن الأفريقي (صحيفة أثير الإلكترونية, 2016)
موروني- سيف المعولييحتوي المعرض المصاحب لمؤتمر " علاقات عمان بدول القرن الأفريقي الذي تنظمه هيئة الوثائق و

رموز الصحافة في زنجبار.. الفلق وكتّابها العمانيون أنموذجا (صحيفة أثير الإلكترونية, 2016)
أثير – تاريخ عمان إعداد – نصر البوسعيدي بلا شك بأن الصحافة تشكل ركنا أساسيّا في نمو الوعي المجتمعي من خلال ما تطرحه من قضايا توعوية تنويرية في شتى المجالات لا سيما وأن الصحافة تعتبر منبرا للش…

الثورة في زنجبار ضدّ العمانيين، والعرب، كيف ولماذا؟! - البوسعيدي, نصر (صحيفة أثير الإلكترونية, 2016)
أثير - تاريخ عمانإعداد- نصر البوسعيديتقع جميع الثورات في العالم نتيجة الظلم، والفقر الذي يتعرض له شعب من الش
Keywords: Vie politique -- Zanzibar -- 1963-1964

The Omani Ruler Who Died Saving His Prisoners (صحيفة أثير الإلكترونية, 2016)

اقترض 12 ريالا عُمانيا..وبعدها أصبح أسطورة عُمانية في أفريقيا (صحيفة أثير الإلكترونية, 2016)
أثير – تاريخ عُمانتيبو تيب حمد بن محمد بن جمعة المرجبي الذي اقتربت شهرته من الأسطورة التي سارت واخترقت سيرته

أحداث رحلة أول حاكم عربي -عماني يزور واشنطن و دول أخرى (صحيفة أثير الإلكترونية, 2016)
أثير – تاريخ عمان: تعتبر رحلة السلطان سعيد بن تيمور في الفترة من 9 نوفمبر 1937م إلى 13 يوليو 1938م من أهم الرحلات التاريخية على مستوى العلاقات بين حكومة مسقط وحكومات الدول التي زارها، إذ بدأ رحلته …
Keywords: Récits de voyage -- Oman

أخلاق العمانيّين في الحرب..الإمام الرحيلي – أنموذجا (صحيفة أثير الإلكترونية, 2016)
أثير – تاريخ عمان:كان آل الرحيل في صحار من كبار علمائها، ولهم مكانة مرموقة بين الجميع، وكان الإمام سعيد بن ع

الجزء الأخير من “تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا” (صحيفة أثير الإلكترونية, 2016)
–        ما الأماكن التي زارها السلطان؟ وكيف كان استقبالهم له؟ –        ما ” المصيبة” التي حدثت قبل سفر السلطان؟ وكم يوما أجّل سفره؟ –        كيف استقبله شعبه بعد رجوع…
Keywords: Récits de voyage -- Oman

ماذا قال واليا مانشستر ولندن وصحيفة التايمز الإنجليزية عن السيد برغش؟ (صحيفة أثير الإلكترونية, 2016)
أثير – تاريخ عمان:بعدما اختتمنا الجزء التاسع بزيارة السلطان برغش لدار الولاية في مانشستر سنكمل الجزء العاشر

الجزء التاسع من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2016)
أثير – تاريخ عمان   في فرجة سعادة السلطان على ميناء ليفربول: أرسل والي مدينة ليفربول غدوة نهار الثلاثاء يطلب إلى سعادة السلطان أن يشرف دار الولاية حتى يسير في صحبته إلى مرفأ السفن، ويفرّجه على…
Keywords: Récits de voyage -- Oman

الجزء الثامن من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2016)
أثير - تاريخ عمان  الجزء الثامن من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م:
Keywords: Récits de voyage -- Oman

الجزء السابع من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2015)
أثير – تاريخ عمان نواصل سرد تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م من خلال هذا الجزء السابع: في حضور سعادة السلطان مأدبة لجنة فيشمنجر: لا يخفى على من له إلمام بأحوال بلاد…
Keywords: Récits de voyage -- Oman

الجزء السادس من تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م (صحيفة أثير الإلكترونية, 2015)
أثير – تاريخ عمان:ذكرنا في ختام الجزء الخامس لرحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا سنة 1875م تفا
Keywords: Récits de voyage -- Oman

تفاصيل رحلة أول سلطان عربي في التاريخ تطأ قدمه بريطانيا (صحيفة أثير الإلكترونية, 2015)
أثير – تاريخ عمان إعداد: نصر البوسعيدي      (1) يدوّن التاريخ في صفحاته بأن العمانيين، وحكّامهم يعتبرون من أوائل العرب الذين شكلوا وفودا رسمية دبلوماسية لزيارة أوروبا، وأمريكا، تلك الدول …
Keywords: Récits de voyage -- Oman

السلطان العماني الذي شارك في الحرب العالمية الأولى (صحيفة أثير الإلكترونية, 2015)
أثير – تاريخ عمان إعداد: نصر البوسعيدي ولد السلطان خليفة بن حارب في مسقط في26/8/1879م لأبوين ينتميان لأسرة البوسعيد الحاكمة في عمان ، فأبوه السيد حارب بن ثويني بن سعيد بن سلطان الذي حكم عمان …
Keywords: Vie politique -- Zanzibar -- 1911-1960

Une tombe datant du IIème siècle Après JC retrouvée à Guellela (Webdo, 2014)
Une tombe avec son mobilier funéraire, en date du IIème siècle après JC a été découverte le 11 juin dans la région de Tlat - Guellala
Keywords: Archéologie -- Djerba

الدور العُماني في نشر الإسلام في القارة السمراء‎ (صحيفة أثير الإلكترونية, 2014)
أثير – تاريخ    تشير الوثائق التاريخية مجتمعة إلى أن قمّة الدور الحضاري الذي أسهم به العُمانيون في القرن الماضي في زنجبار كان في مجال الدعوة الإسلامية التي كانت…

” كينجوجوا” الاسطورة العمانية المغامرة في أدغال أفريقيا (صحيفة أثير الإلكترونية, 2014)
تيبو تيبحمد بن محمد بن جمعة المرجبي(1840- 1905)أسطورة المغامرة في أدغال أفريقيا  تاريخ - أثير &nb

Hichem Mechichi à la synagogue de la Ghriba à Djerba: La chechia chinoise fait polémique | Tekiano :: TeK'n'Kult (2021)
A l'occasion de la visite annuelle de la synagogue juive de la Ghriba, ou le pèlerinage de la Ghriba à Djerba qui a coincidé cette année avec le Ramadan 2021...
Keywords: Judaïsme -- Djerba

En Tunisie, le pèlerinage juif de la Ghriba ouvert dans la sobriété - Eblotié, Guy Aimé (La Croix Africa, 2021)
Le pèlerinage juif de la Ghriba sur l’île de Djerba, en Tunisie, s’est ouvert, lundi 26 avril, dans la sobriété imposée par les mesures sanitaires
Keywords: Judaïsme -- Djerba

La peur s’installe dans la communauté juive de Djerba - Zis, Eliezer (JForum, 2021)
les Juifs tunisiens vivent à nouveau dans la peur
Keywords: Judaïsme -- Djerba

Et Djerba devenait le 25e gouvernorat en Tunisie ? - Bessais, Raja (Webmanagercenter, 2021)
Le chef du gouvernement, Hichem Mechichi, a annoncé qu’une séance de travail sera organisée fin mars 2021 pour examiner le dossier de l’attribution à Djerba du statut de gouvernorat. Lors d’une rencontre à Djerba - qui relève du gouvernorat de Médenine - avec les représentants de l’Union ré…

“Manuscripts are like vampires” (article in History Compass, 2020) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2021)
A screenshot of my most recent article, “Manuscripts are like vampires” (History Compass, 2020), available online here: I have been super busy with a couple of grant applications for th…
Keywords: Manuscrits -- Djerba

Djerba : Le couscous à six mains enchante l'Unesco - Bourial, Hatem (Webdo, 2020)
Elles sont trois et elles ont préparé un couscous à six mains, ces derniers jours à Djerba. Il s’agit ainsi de trois couscous aux poissons préparés par Annie Kabla, Jacqueline Camilleri-Louati et Coco Dora. Les trois amies ont cuisiné trois couscous différents aux poissons. Le premier est un couscous à la façon maltaise de Djerba, […]
Keywords: Alimentation -- Djerba

Tracing the history of Ibāḍī law and jurisprudence: A state of art - Francesca, Ersilia (Islamic Law Blog, 2020)
This essay is part of the Islamic Law Blog’s Roundtable on Islamic Legal History & Historiography, edited by Intisar Rabb (Editor-in-Ch…

La visite d'Heinrich Barth chez Soliman Ben Ayed. (Palais BEN AYED à Djerba, 2020)
Soliman Ben Ayed un homme fort sympathique, de grande stature, au visage majestueux ornée d’une barbe à la couleur blanche argentée.
Keywords: Famille Bin Ayyad

Le PNUD soutient la gestion des déchets de soin à Djerba - Bessais, Raja (Webmanagercenter, 2020)
Une formation de 3 jours a été organisée au profit d’un groupe restreint d’agents du Groupement de Santé de Base de Djerba pour le renforcement de leurs capacités dans le domaine de la gestion des déchets de soin au sein des établissements hospitaliers dans le contexte de la pandémie de COVI…
Keywords: Crises environnementales -- Djerba

La Boukha Djerbienne de Houita Kabla - Bourial, Hatem (Webdo, 2020)
Il existait quelques distilleries à Djerba jusqu’au début des années soixante. La plus connue n’est autre que la Distillerie nouvelle que gérait la famille Kabla. Cette famille avait son usine à l’entrée de Houmt Souk et produisait une boukha de qualité avec des figues et des raisins secs de premier choix. Annie Kabla vient de […]
Keywords: Artisanat -- Djerba

Arabic manuscripts to print (and back again) | من المخطوط إلى المطبوع…والعودة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
When an Arabic text had appeared in print, there was no reason to copy it by hand anymore, right? Not quite. The reality is way messier and far more interesting.

Book Review: “The Ibadi presence in Egypt” | مراجعة كتاب: الوجود الإباضي في مصر - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
The cover of al-Wujūd al-Ibāḍī fī Miṣr (Maktabat Khazāʾin al-Āthār, 2018). I borrow the image here from a remarkably detailed summary of the book available in Arabic here. I recently had the pleasu…
Keywords: Recension

An Ibadi sultan at the Khedive’s dinner party (1875) | سلطان إباضي عند طاولة الخديوي للعشاء (1875) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
(Tawfīq Pāsha) “Do you have wine in your country?” (Sultan Barghash) “Yes, we have wine made of date palms. The dissolute (al-fasaqa) drink it—in secret. When it gets the be…

Ibadi Manuscripts at the Dār al-Kutub in Egypt (Part 2, the Inventory) | المخطوطات الإباضية في دار الكتب المصرية (الجزء الثاني, الجرد) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
Ayman Fuʾād Sayyid, Fihrist al-makhṭūṭāt nashra bi-‘l-makhṭūṭāt allatī aqtanathā al-dār min sanat 1936-1955. 3 Vol.s (Cairo, 1961-1963). This is a brief follow up to the previous post about I…
Keywords: Manuscrits -- Le Caire

Ibadi Manuscripts at the Dār al-Kutub in Egypt (Part 1)| المخطوطات الإباضية في دار الكتب المصرية (الجزء الأول) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
A couple of years ago, I received a photocopy of some handwritten notes on Ibadi manuscripts in the Egyptian National Library, the Dār al-Kutub al-Miṣriyya (Figure 1). The notes are dated 1408/1988…
Keywords: Manuscrits -- Le Caire

The library of Ibadi historian Saʿīd b. ʿAlī b. Taʿārīt (d.1289/1872) | مكتبة المؤرّخ الإباضي سعيد بن علي بن تعاريت - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
Saʿīd b. ʿAlī b. Taʿārit (d.1289/1872) occupies an important place in the history and historiography of Ibadi communities in the Maghrib as the author of The Epistle on the History of Jerba (Risāla…
Keywords: Manuscrits -- Djerba

« Bassamat Opéra » à Djerba : Des acteurs à besoins spécifiques en devenir - Haouel, Haithem (La Presse de Tunisie, 2020)
Une appellation recherchée pour un projet dirigé par le Dr Zouhair Ben Tardayt. Le laboratoire permettra aux enfants et aux adolescents à besoins spécifiques, déficients mentaux ou physiques, à améliorer leurs acquis, leurs savoirs, à les aider à mieux s’intégrer socialement, à avoir davantage confiance en eux, à faire surgir des dons cachés entre autres, grâce à la scène, à la maîtrise de la parole en public, à l’art scénique libre et ses différentes expressions, aux arts en général : costumes, musique, théâtre, cinéma et projections. Scénographie, lumière… Le projet les mènera à la création et à présenter un travail accompli au final.
Keywords: Théâtre -- Djerba

Call for Participants: Workshop on Ibadi Manuscripts in European/North American Libraries | إعلان بطلبة مشاركين في الورشة الثانية حول المخطوطات الإباضية: “المخطوطات الإباضية بالمكتبات الأوروبية” - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
Organizers of the second annual Workshop on Ibadi Manuscripts and Manuscript Cultures are delighted to invite proposals from participants under the theme: “Ibadi Manuscripts in European and N…

The Ifrane Collection: a non-Ibadi Library (for a change)| رصيد إفران :مكتبة غير إباضية (لتغيير الجو) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
“The Ifrane Collection,” is a remarkable private collection of mostly-Sufi titles from here in Morocco. It includes more than a dozen copies of Muḥammad b. Sulaymān al-Jazūlī’s (d…
Keywords: Bibliothèques -- Maroc

Découverte à Djerba d'une plante unique au monde - I.B. (Webdo, 2019)
Une spécialiste en botanique a annoncé que l’ile tunisienne de Djerba accueille une plante unique au monde : il s’agit du Formosum Delimonium, une plante rare dans le monde n’a été trouvée que sur l’île de Djerba. Selon le docteur Zeineb Gharbi Kammar, si cette plante n’est pas entretenue et protégée à Djerba, elle disparaîtra du […]
Keywords: Formosum Delimonium -- Djerba

Ibadis in Midrarid Sijilmasa |الإباضية في مدينة سجلماسة المدرارية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Ibadisme -- Sijilmasa

Naples MS ARA 50 | مخطوط رقم ٥٠ في جامعة نابولي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Manuscrits -- Naples

قائمة أولية من الخزائن الجربية في القرن العشرين | A Preliminary List of Djerbian Libraries in the 20th century - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Catalogue -- Djerba

The (Almost) Lost Siyar of Jabal Nafusa | سير مشائخ جبل نفوسة (التي كادت تُفقد) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba; Prosopographie -- Djebel Nefousa

A Letter from the archive about Sedrata and Abū Zakariyā al-Warjalānī | رسالة من الأرشيف حول سدراتة وأبي زكرياء الورجلاني - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Archives -- Aix-en-Provence

Amr Ennami in Michigan |المرحوم الدكتور عمرو النامي في ميشيغان - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Ennami, Amr (1939-198X)

An Ibadi Bookstore in Tunis | مكتبة إباضية في تونس - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
While visiting Tunis this month I stopped by to see my friend Mohamed Bennani, owner of what is for me one of the most eclectic and fascinating book and ephemera collections in Tunisia (the “…
Keywords: Bibliothèques -- Tunis

Al-Bārūnī Library in Djerba | فتح المكتبة البارونية في جربة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Bibliothèques -- Djerba

Les Amants Infidèles - Ben Jemaa, Zouhair (Réalités Online, 2016)
DJERBA est encore douce, toujours fidèle, mais Djerba est triste, et son cœur saigne tant ses amants la délaissent et la négligent ! Qui l’eût cru ? Après tant d’efforts et tant d’investissements, comment peut-on abandonner un tel paradis ? Nos responsables ont tord de ne pas avoir capitalisé sur la singularité de l’île et […]
Keywords: Tourisme -- Djerba

Text of the Presentation from the Cheikh Sālim b. Yaʿqūb Symposium | نص المداخلة من ملتقى الشيخ سالم بن يعقوب - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)

3rd Annual Conference in honor of Cheikh Sālim b. Yaʿqūb in Djerba | الملتقى الثالث لجمعية الشيخ سالم الثقافية في جربة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2016)
Keywords: Biographies -- Djerba -- 20e siècle

مكتبة البعطوري في جزيرة جربة | The Buʿṭūrī Manuscript Library in Djerba - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)
Keywords: المكتبة البعطورية

جربة التونسية جزيرة الأحلام: تناغم فريد بين الطبيعة الخلابة وآثار حضارات متعاقبة - حاج إبراهيم, سليمان (القدس العربي, 2015)
جزيرة جربة ـ «القدس العربي»: تونس التي تعيش مخاضا عسيرا منذ ثورة كانون الثاني/يناير 2011 وخلع رئيسها السابق بن علي، وما سجلته من انفلات أمني هدد استقرار البلاد، تضيء (جزيرة جربة) في جنوبها مركز إشعاع بلجت أنواره في السديم الذي يعكر سماء الخضراء لتزرع الأمل بغد أفضل بما تختزنه في رصيدها من إرث تليد حافظ عليه سكانها وصانوه بتناغم مجموعاتهم المتآلفة.
Keywords: Récits de voyage -- Djerba

Unsewn Textblocks in Ibāḍī MSS | مخطوطات إباضية غير مخيطة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)

On Marbled Papers | حول الأوراق "الرخامية" - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)

زيارة إلى الميزاب | A visit to the Mzab - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)

Ibadi Islam - a look into one of Islam's earliest school of thought (International Shia News Agency, 2015)
SHAFAQNA – The  Ibadi school of thought is one of the main branches of Islam. The main difference between the Ibadis and the rest of the Muslim community is primarily rooted in political theory. The Ibadis are relatively few in number in comparison to the Sunnis and the Shias and for many centuries they have […]
Keywords: Ibadisme -- thèmes et motifs

Ibadi Related Documents at the Archives Nationales d'Outre Mer | وثائق متعلّقة بالإباضية في الأرشيفات الخارجية الفرنسية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)
Keywords: Archives -- Aix-en-Provence

Barouni Manuscript Library, a Livre d'Or | المكتبة البارونية: كتاب التسجيل - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)
Keywords: Bibliothèques -- Djerba

Cheikh Salim Seminar in Djerba & the Salim b. Yaʿqūb Library | ملتقى الشيخ سالم الثقافي في جربة ومكتبة سالم بن يعقوب - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2015)
Keywords: Bibliothèques -- Djerba

Ibadi MSS at the Univ. of Naples "L'Orientale" | المخطوطات الإباضية في جامعة نابولي الشرقية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Manuscrits -- Naples

Association pour la sauvegarde de l'île de Djerba (Part 1): Manuscripts | جمعية صيانة جزيرة جربة (الجزء الأول): المخطوطات - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

Some Observations on Watermarks from the Barouniyya Library | ملاحظات حول العلامات المائية من المكتبة البارونية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Djerba

Bookworms, literally | دود الكتب...فعلا - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Manuscrits -- Djerba

Degree Distributions in Ibāḍī Prosopographies | توزيع الروابط في البروسوبوغرافيات الإباضية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Prosopographie -- Afrique du Nord

Cytoscape & Other Tools | أدوات جديدة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Prosopographie -- Afrique du Nord

Distribution of Ibāḍī Scholars | توزيع العلماء الإباضية الجيوغرافي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Prosopographie -- Afrique du Nord

Ibāḍī Prosopographical Manuscript Database | قاعدة بيانات المخطوطات البروسوبوغرافية الإباضيّة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Prosopographie -- Afrique du Nord

Some New Books on Ibadi History | بعض الكتب الجديدة حول التاريخ الإباضيّ - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)

Geographic Distribution (1st-15th century AH) Video Posted - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Prosopographie -- Afrique du Nord

Intellectual Network Map: 5th/11th Century | خريطة شبكة علمية: ق ٥/١١ - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Network Map: Trial Run! - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Geo-Distribution of Ibadi Scholars: Charts Posted - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Geographic Distribution of Ibāḍī scholars - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

Mapping Ibāḍī Scholars across the Centuries: Experimental Stage 1 - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Prosopographie -- Afrique du Nord

List of Ibāḍī Manuscripts at BNT in Tunis | قائمة المخطوطات الإباضية في المكتبة الوطنية التونسية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Manuscrits -- Tunis

Recent Conferences on Ibadism - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)

Ibadi MSS at the Bibliothèque Nationale de Tunisie - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2013)
Keywords: Manuscrits -- Tunis

Vient de paraître «Patientes» de Hayet Barbouch-Safraoui : «Elles étaient une fois ! » - Trabelsi, Salem (La Presse de Tunisie, 2012)
«Patientes » est un recueil de nouvelles écrit par Hayet Barbouch-Safraoui qui rend hommage à ces monuments de patience, à ces Djerbiennes fortes et
Keywords: Littérature -- Djerba

Djerba: l’étude du schéma d’aménagement de la zone sensible validée (L'Economiste Maghrébin, 2020)
L'étude du nouveau schéma directeur d'aménagement de la zone sensible de l'île de Djerba a été validée, mercredi 16 décembre 2020.
Keywords: Urbanisme -- Djerba

المستشرق البولوني تادايوش ليفيتسكي…والتراث الإباضي - بسكر, محمد (البصائر, 2020)
أ. محمد بسكر / انبعاث التاريخ من خلال المخطوطات سمة مميزة للأبحاث التاريخية التي وضعها المستشرقون ال
Keywords: Orientalisme -- Pologne

L’importanza di essere Mascate - Mazzocco, Andrea (geopolitica, 2020)
Sistematicamente adombrato da ingombranti vicini, di rado l’Oman conquista i titoli dei notiziari, risultando il più delle volte un oggetto misterioso anche a buona parte degli addetti ai lavori. In effetti, se raffrontato alle altre monarchie del Golfo, tale eclissi sembra essere pienamente meritata; penultimo per riserve di greggio, di gas e per PIL, estraneo all’inesauribile confronto tra sunnismo e sciismo e contraddistinto da una politica estera equidistante, Mascate non sembra avere i titoli per accreditarsi come game-changer nell’area. Sarebbe però un errore considerare il Paese un semplice satellite di Riyad o peggio un anacronistico retaggio dell’epoca coloniale, in quanto le sue peculiarità lo rendono un unicum nel composito panorama del Golfo.

Fadhel Jaziri à La Presse : «Notre politique culturelle n’est plus articulée sur un marché» - Trabelsi, Salem (La Presse de Tunisie, 2020)
L’acteur et réalisateur Fadhel Jaziri a choisi l’île de Djerba pour construire un grand centre culturel, destiné également à la production. Il nous en
Keywords: Vie culturelle -- Djerba

A surprising lithograph at the American University in Cairo | طبعة حجرية إباضية في مكتبة الجامعة الأمريكية في القاهرة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
Unable to travel lately, I have been searching for Ibadi lithographs listed in research libraries online. .. I did not anticipate [finding] the former owner of these volumes…
Keywords: Manuscrits -- Le Caire

René Trabelsi : Un gouvernorat "Djerba 25" n'est pas forcément la bonne solution - Bchir, Nadya (Radio Express FM, 2020)
Depuis l’île des rêves Djerba, le plateau de l’émission Expresso du vendredi 16 octobre 2020 a invité l’ancien ministre du Tourisme, René Trabelsi afin de parler du modèle de développement économique adopté à l’île. Il a, à cet effet, que Djerba a connu une période très difficile eu égard au fait que 80% de ses…
Keywords: Djerba -- Gouvernorat

Ibadi Manuscripts in non-Ibadi Libraries | المخطوطات الإباضية بالمكتبات غير الإباضية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
Ibadi libraries, almost without exception, house non-Ibadi books. Sometimes, Ibadi-owned libraries held hundreds of titles by non-Ibadi authors and those titles far outnumbered the Ibadi ones. When…
Keywords: Manuscrits -- Djerba

مشاركة بحثية عمانية في ندوة ثقافية أقيمت في جزيرة جربة بتونس الموقع الرسمي لجريدة عُمان (الموقع الرسمي لجريدة عُمان, 2019)
نزوى – مكتب عمان – شارك مجموعة من الباحثين العمانيين في الندوة الدولية لكتب السير الإباضية، التي أقيمت في جزيرة

Ibadi Lithographs at McGill University’s Rare Books Library | مطبوعات حجرية إباضية في مكتبة جامعة مكيل في كندا - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
The Rare Books Library at McGill University in Montreal, Canada has a small collection of Ibadi lithographs from Algeria and Egypt [1]. And (at least) one of them has a very unexpected story. The f…
Keywords: Manuscrits -- Canada

EAP1216 “The Djerba Libraries Project:” A New Manuscript Digitization Project in Djerba, Tunisia | مكتبات جربة: مشروع جديد لرقمنة المكتبات بجربة (تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
I am delighted to announce the launch of “EAP1216 The Djerba Libraries Project,” a two-year effort to digitize several libraries on the island of Djerba, Tunisia. Funded by Arcadia (a c…
Keywords: Manuscrits -- Conservation; Manuscrits -- Djerba

Ibadi binding covers from the Mzab Valley | أغلفة المخطوطات الإباضية بوادي مزاب - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
A few years ago, I wrote a short post on unsewn textblocks in Ibadi manuscripts in the Maghrib. That idea was connected to some preliminary conclusions by codicologist and conservator Karin Scheper…
Keywords: Manuscrits -- Mzab

Baha’is and Ibadis in the Tunisian Archives | البهائيون والإباضية في الأرشيف التونسي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
This month I am back in Tunis to visit the Tunisian National Archives, where I am able to spend a few weeks doing research thanks to an AIMS Short-Term Research Grant (Thanks, AIMS!). I am here bec…
Keywords: Archives -- Tunis

The Mzabi Confectioner of Istanbul: a story from the archives of the 19th century | الحلاوي المزابي في إسطانبول: قصة من أرشيفات القرن التاسع عشر - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
On 12 September 1878, Hadj Ahmed Ben Othman El Mzabi died in the Valide Sultan hospital in the Sultan Mahmud quarter of Istanbul. He had been working in the Ottoman capital as a confiseur, or &#821…
Keywords: Emigration -- Mzab -- Turquie

Jerba in European Archives: The Ben Ibrahim Family & the Consulates of France and Britain in the 19th century | جربة في الأرشيفات الأوروبية: عائلة “بن إبراهيم” وقنصليات فرنسا وبريطانية في القرن التاسع عشر - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
This week, I am in France at the Centre des Archives diplomatiques de Nantes looking for documents connecting Ibadis in Jerba and Cairo. I did a similar visit in January to the British National Arc…
Keywords: Archives -- Nantes

Recent Article on the Buffalo Agency & an Apology to Augustin Jomier | مقال جديد حول وكالة الجاموس واعتذار للأستاذ أغوطان جومي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
An article of mine recently appeared at the end of last year (2018)  in the Journal of Islamic Manuscripts (Brill) entitled “Ibadis on (and in) the Margins: Manuscript Notes from the Buffalo …

The owners and life cycle of Ibadi Manuscripts: AK157 from the Buffalo Agency | أصحاب المخطوطات الإباضية ومراحل حياتها: “أك١٥٧” من وكالة الجاموس نموذجا - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
As part of a project on the history of the Ibadi community in Cairo in the Ottoman period, I have been looking through digital facsimiles of manuscripts from the private library of Shaykh Aḥmad al-…
Keywords: Manuscrits -- Le Caire

Program for the Workshop on Ibadi Manuscripts and Manuscript Cultures 2019 | البرنامج للورشة الدولية حول المخطوطات الإباضية وثقافة المخطوطات عند الإباضية ٢٠١٩ - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
We are delighted to welcome ten participants to Al Akhawayn University in Ifrane this Friday and Saturday (5-6 April 2019) for what we hope is the first of many paper workshops on “Ibadi Manu…

Ibadi connections: Tripoli, Cairo, Baghdad, & Muscat during World War II | الروابط الإباضية: طرابلس والقاهرة وبغداد ومسقط في الحرب العالمية الثانية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
As part of an ongoing project on the history of the Ibadi community in Cairo, I have been looking into the later life of the famous Ibadi activist, revolutionary, and diplomat Sulaymān al-Bārūnī. T…

From the Jebel Nafusa to Cairo: Notes on Ibadi Print Culture and the Buffalo Agency (part 2: Qāsim al-Shammākhī) | من جبل نفوسة إلى القاهرة: ملاحظات حول ثقافة الطباعة عند الإباضية ووكالة الجاموس (الجزء الثاني: قاسم الشماخي) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2019)
I return here to the first Ibadi newspaper published in Cairo in the 20th century: the Nibrās al-Mashāriqa wa-‘l-Maghāriba, which was recently published in one volume Oman in 2014 (ed. Ṣulṭān…
Keywords: Journalisme -- Le Caire

Where oil and water mix: the Omani papers of John Craven Wilkinson (EUL MS 119) | Special Collections (2019)
Keywords: Archives -- Exeter

Entretien avec Abdulrahman Al-Salimi - IslamXXI (L'islam au xxie siècle, 2019)
Sheikh Dr. Abdulrahman Al-Salimi revient sur une spécificité du royaume, l'ibadisme et la contradiction entre Islam et droits naturels - Conférence Paris UNESCO 26-27 fév 2019
Keywords: Ijtihad

From the Jabal Nafusa to Egypt: Notes on Ibadi Manuscripts, Print Culture, and the Buffalo Agency in Cairo (part one) | من جبل نفوسة إلى مصر: ملاحظات حول المخطوطات الإباضية وثقافة الطباعة ووكالة الجاموس في القاهرة (الجزء الأول) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
Thanks to the good folks over at Ibadica in Paris, I recently obtained a copy of the printed edition of the first Ibadi newspaper from Cairo, the Nibrās al-mashāriqa wa-‘l-maghāriba (ed. Ṣulṭ…
Keywords: Manuscrits -- Le Caire

Sulaymān Bāsha al-Bārūnī: A CV in English | سليمان باشا الباروني: سيرة ذاتية بالإنجليزية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
It’s been a busy semester of classes and I haven’t had much time to write. When I saw one particular document from the British Archives today, however, I decided to make time. The docum…
Keywords: Bārūnī, Sulaymān al- (1870-1940)

الصحفي المناضل: الشيخ سليمان الجادوي 1871-1951 (القومية التونسية, 2018)
الرجل الذي كتب منذ سنة 1906 فأنشأ ثلاث جرائد، غرم و سجن بسببها و
Keywords: الجادوي، سليمان (1871-1951)

Oddments from a “Nukkārī” Ibadi Library: the al-Ṣāṭūrī Library in Jerba, Tunisia | بقايا من مكتبة “نكارية”: مكتبة الصاطوري بجزيرة جربة (تونس) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
Over the past several years, I have worked with private manuscript collections belonging to families in Jerba, Tunisia. The island is home to several well-known libraries, including those belonging…
Keywords: Bibliothèques -- Djerba; Nukkarisme

Intersections between Manuscript and Lithograph Cultures in Private Libraries | التداخلات بين ثقافتَي المخطوطات والطبعات الحجرية في المكتبات الخاصّة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
Historians interested in Ibadi and other Arabic manuscripts (including me) often treat manuscripts separately from printed materials in private libraries. But in the second half of the 19th century…
Keywords: Bibliothèques -- Djerba

Catalog of Ibadi & Other Arabic Manuscripts at the Association pour la sauvegarde de l’île de Djerba (ASIDJ) | فهرس المخطوطات الإباضية وغيرها من المخطوطات العربية في مكتبة جمعية صيانة جزيرة جربة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
After a series of short visits beginning in 2014 and ending just this week, I’m delighted to offer a preliminary catalog of Ibadi and other Arabic manuscripts held at the library of the Assoc…
Keywords: Catalogue -- Djerba

Destroy a mosque they prayed in… imprison them, and beat them | هدم مسجد كانوا يصلون فيه…سجنهم وضربهم - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
This post comes from a handful of fatwas I ran across in the famous Miʿyār al-Muʿrib of the 15th-century North African scholar Aḥmad al-Wansharīsī (d.914/1508). It turns out that this amazing colle…
Keywords: Polémique wahhabite

Workshop on Ibadi Manuscripts (2019)| ورشة عمل حول المخطوطات الإباضية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
I am delighted to announce the call for participants in an upcoming workshop entitled “Ibadi Manuscripts and Manuscript Cultures” to be held from 5-6 April 2019 at Al Akhawayn Universit…
Keywords: Manuscrits

Preserving Endangered Archives in Jerba, Tunisia: The al-Bāsī Family Library | الحفاظ على الأرشيفات المهدّدة في جربة: مكتبة الباسي العائلية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
The Journal of Manuscript Studies (3:1, Spring 2018) has just published a short research annotation by my colleague Dr. Ali Boujdidi and myself, describing our project on the El Bessi (al-Bāsī) fam…
Keywords: Manuscrits -- Conservation; Manuscrits -- Djerba

New Online Resource for Ibadi and Omani Manuscripts & Newspapers | مرجع جديد للبحث حول المخطوطات الإباضية والجرائد متوفّر في الإنترنت - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
I was delighted to learn this past week of an amazing new collection of digital facsimiles of Ibadi manuscripts and related newspapers from Oman, Zanzibar, and the Mzab published online by the Oman…

Unexpected Connections: Musa Bey Grada, the Ottomans, and the Buffalo Agency | روابط غير متوقعة: موسى بيك قرادة، العثمانيون، ووكالة الجاموس - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
While working on an article on the history of Ibadi manuscripts at the Università degli Studi di Napoli L’Orientale (UNO) in Naples, I ran across an interesting connection between that articl…

وفاة العالم القدير الشيخ سالم بن يعقوب (تين ؤسّان, 2018)
حدث في مثل هذا اليوم 26 يناير 1991 وفاة الشيخ المؤرخ سالم بن محمد بن يعقوب الجربي أحد أهم أعلام المذهب الإباضي المعاصرين في جزيرة جربة كان بدون منازع يملك أكبر مكتبة مخطوطات (إذا إستثنينا البارونية التي هي في الأصل نفوسية) . وولد في قرية غيزن (ربما يكون من أواخر من تحدث بالأمازيغية في هذه …
Keywords: Biographies

Upcoming Public Exhibition for al-Bāsī Library Project in Djerba, Tunisa: معرض مكتبة الباسيين في جربة - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
It is my pleasure to announce the upcoming public exhibition of “Conserving Endangered Archives in Jerba: the al-Bāsī Family Library Project” in Djerba, Tunisia, taking place this comin…
Keywords: Manuscrits -- Djerba

Abū Yazīd Makhlad b. Kaydād, the Jihadist | أبو يزيد مخلد من كيداد، الجهادي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2018)
[تنبيه: الترجمة العربية ستأتي بعد] Ibadis appear in surprising places—including late-20th century Jihadist literature. This post is about an unexpected use of the story of the famous 10th-century I…
Keywords: Ibn Kaydad

Ibadi Manuscripts in Naples| المخطوطات الإباضية في نابولي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
I am delighted to announce that I have now posted an inventory and catalog of the Ibadi manuscripts held at the Special Collections Library of the Università degli Studi di Napoli L’Orientale in Na…
Keywords: Manuscrits -- Naples

Announcing a new manuscript conservation effort in Djerba, Tunisia: the El Bessi Library Project | إعلان بمشروع جديد للحفظ على المخطوطات في جزيرة جربة: مشروع مكتبة جامع الباسي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Bibliothèques -- Djerba; Manuscrits -- Conservation; Manuscrits -- Djerba

An Ibadi Manuscript at Columbia University (Part 3/3)| مخطوط إباضي في جامعة كولومبيا (٣/٣) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Manuscrits -- Etats-Unis

An Ibāḍī Manuscript at Columbia University (Part 2!) | مخطوط إباضي في جامعة كولومبيا (المتابعة) - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Manuscrits -- Etats-Unis

An Ibadi Manuscript at Columbia University | مخطوط إباضي في جامعة كولومبيا - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Manuscrits -- Etats-Unis

Lancement du premier incubateur au sud Tunisien (tuniscope.com, 2020)
Après la création de COZI COWORKING SPACE à DJERBA en 2016, le COZI BUSINESS INCUBATOR vient d'apparaître pour favoriser l’entrepreneuriat et la création de startup au sud tunisien et de contribuer ainsi à la génération de l’emploi et de la richesse en partenariat avec USAID Tunisia Jobs.
Keywords: Développement local -- Djerba

Médenine-covid19 : Nouvelles mesures préventives pour freiner la propagation du virus (Directinfo, 2020)
Les municipalités de Zarzis et Zarzis-Nord (gouvernorat de Médenine) ont décidé de nouvelles mesures préventives face à l'augmentation
Keywords: Covid-19 -- Djerba

Caserne de Djerba: Intoxication alimentaire pour 29 agents (Réalités Online, 2020)
29 agents des Brigades de l’ordre public appartenant à la caserne d’Al Kantara, à l’entrée de l’ile de Djerba ont été victimes d’une intoxication alimentaire après avoir pris leur déjeuner dans cette caserne, mercredi 11 novembre, rapporte Sabra FM. Ils ont été transportés à l’hôpital régional Sadok Mkadem de Houmet Souk où ils ont reçu […]

Djerba : Life en reportage à Hara Sghira - Bourial, Hatem (Webdo, 2020)
Keywords: Judaïsme -- Djerba

Tunisie, retrouvailles séfarades à Djerba - Prevost, Virginie; Derriks, Axel (Mondafrique, 2018)
Tunisie, Djerba. Les juifs célébreront Lag Ba Omer le 3 mai et se rassembleront pour le pèlerinage de la Ghriba. Les juifs de Tunisie et du monde entier
Keywords: Judaïsme -- Djerba

A Djerba, le mausolée des martyrs ottomans du siège de 1560 - Bourial, Hatem (Webdo, 2017)
Ce mausolée est minuscule, peu connu et n’a été restauré que depuis quelques années. Pourtant, il témoigne d’un épisode historique de première importance. En février 1560, les soldats de la flotte espagnole s’étaient en effet emparés du borj Ghazi Mustapha après un assaut qui avait surpris la garnison qui se trouvait sur place. Les Espagnols qui en ce temps croisaient le fer avec les Turcs pour la domination de la Méditerranée avaient ainsi marqué un point dans une période des plus troublées. Se réorganisant rapidement, faisant appel à des renforts, les Ottomans allaient vite reprendre le fort disputé. Les escarmouches dureront de mai à juillet et s’achèveront par la libration du fort principal de Djerba. Une modeste plaque et un mausolée regroupant quelques tombes rappellent cet épisode de notre histoire et les clameurs des vaisseaux de guerre en Méditerranée. C’est aussi la mémoire de Khereddine, Barberousse et Dragut qui est évoquée par ce mausolée, l’un des rares qui témoignent des luttes entre Ottomans et Espagnols pour le contrôle des côtes tunisiennes.
Keywords: Invasions chrétiennes -- Djerba -- 1560

Tourisme : Djerba à l'honneur aux Fêtes Consulaires de Lyon - Elouati, Mehdi (Webdo, 2017)
Tribune | Mehdi Louati « Lyon Invite Djerba », une première initiative de l’ONTT et les fédérations de Tourisme en collaboration avec le Consulat de Tunisie à Lyon. En effet, cette rencontre du 1er et 2 juillet 2017, est venue en faveur avec le nouveau découpage territorial basé sur la décentralisation pour que des régions comme Djerba […]
Keywords: Tourisme -- Djerba

À Djerba, Chikh Yahya le coin de paradis enchanté par la communauté Ijou Gdena - Elouati, Mehdi (Huffington Post Maghreb, 2017)
Keywords: Tourisme -- Djerba

Djerba : La beauté immaculée de la mosquée Sellaouati - Bourial, Hatem (Webdo, 2017)
Dans l’île de Djerba, le bleu du ciel et de la mer se confond avec la blancheur des mosquées. Repassées à la chaux, bucoliques car souvent celées au plus profond des campagnes, ces mosquées sont en effet repassées à la chaux et surgissent au détour d’un chemin, entre les sillons d’un champ et les reflets d’un coucher de soleil. Similaires dans leur architecture rustique aux « menzels », ces manoirs djerbiens, les mosquées sont partout! Qu’elles ressemblent à des forteresses ou qu’elles veillent sur le large, elles témoignent d’une architecture sobre et surprennent par cette blancheur éclatante. L’une de ces mosquées singulières se trouve non loin de Mezraya, entre Midoun et Houmt Souk. C’est de la mosquée Sellaouati qu’il s’agit dont la construction remonterait au seizième siècle lorsque le clan des Sellaouates s’installa dans cette région fertile. Une légende de fondation entoure la naissance de cette mosquée. On raconte ainsi qu’après avoir creusé un puits, les Sellaouates décidèrent d’établir leur lieu de culte. Ils allaient commencer à bâtir l’édifice lorsqu’ils constatèrent la présence d’une colonne de marbre qui affleurait du sol. Ils reçurent comme un signe divin l’existence de cette colonne et décidèrent d’établir leur mosquée en y incorporant ce vestige d’une autre époque. Le sanctuaire fut alors construit avec simplicité et l’édifice achevé, on s’engagea à y prier le lendemain. C’est ainsi qu’à l’aube, les membres de la communauté se retrouvèrent devant leur mosquée. Toutefois, mystérieusement, la porte en était close. Malgré l’absence de serrures et de loquets, la porte refusait de s’ouvrir. Ne sachant comment s’y prendre, ils retournèrent la question dans tous les sens. Mais rien n’y fit. Ils se résolurent alors à demander conseil à une femme vénérable reconnue de tous pour sa sagesse. Elle leur indiqua qu’il fallait qu’ils s’acquittent de leur devoir de charité pour que la porte s’ouvre devant eux. Aussitôt dit, aussitôt fait! Du pain fut enfourné et distribué aux indigents alentour. Un dernier pain fut gardé par le cheikh qui l’émietta devant la mosquée. C’est alors que la porte consentit à s’ouvrir enfin… Depuis, cette mosquée massive au minaret carré continue à recevoir les fidèles et, parfois, de simples curieux allés à la quête de ce sanctuaire immaculé qui se cache derrière les oliviers et cèle en lui une tradition de plusieurs siècles…
Keywords: Architecture -- Djerba

Djerba : Il était une fois Romdhane Ben Mahmoud. Histoire d'un magicien de la poterie - Elouati, Mehdi (Huffington Post Maghreb, 2016)
Keywords: Artisanat -- Djerba

Avec l’association Djerba Insolite, des jeunes veulent promouvoir le tourisme alternatif, écologique et culturel de l’île de Djerba - Smati, Maha (Huffington Post Maghreb, 2016)
Keywords: Tourisme -- Djerba

Découvrez Oncle Mohamed, artisan de tapis de nattes à Djerba depuis l’âge de douze ans - Smati, Maha (Huffington Post Maghreb, 2016)
Keywords: Artisanat -- Djerba

Djerba : hommage à Hamadi Louati ... - Elouati, Mehdi (Wepost, 2016)
Hamadi LOUATI La disparition de cet homme est une grande perte, pas seulement pour sa famille, mais pour la Tunisie. Mohamed Mongi LOUATI né le 18 janvier 1935, souvent sa mère Zelha le taquinait « Hamadi » pour que ce surnom amoureux lui demeure collé toute sa vie. Son père Hassine était commerçant au Maroc,…

Djerba, l’île de la cinquième saison - Bourial, Hatem (Webdo, 2015)

Après le pèlerinage de la Ghriba, la communauté juive célèbre Shavuot - Bourial, Hatem (Webdo, 2015)
Le pèlerinage de la Ghriba vient de s’achever à Djerba et c’est au tour de la fête de Shavuot d’être célébrée. Cette fête marque la fin du décompte du « Omer » et se célèbre 17 jours après la « hiloula » de la Ghriba. Shavuot est connue comme la Pentecôte juive et se réfère à l’acceptation de la Torah par les Hébreux, réunis au pied du Mont Sinaï, alors que Moise reçoit les Tables de la Loi. Cette année, Shavuot sera célébrée les 24 et 25 mai. En Tunisie, le 23 mai, veille de la fête, on a coutume de décorer les maisons et les synagogues avec des fleurs. On allume aussi des bougies et on récite le « kiddouch ». De plus, un dîner festif a lieu en cette veille de Shavuot. Enfin, les plus pieux, surtout parmi la communauté juive de Djerba, passent la nuit en prières et lisent la Torah jusqu’à l’aube. Dimanche 24 mai est le premier jour de la fête. Les solennités consistent essentiellement à se rendre à la synagogue et avoir un nouveau dîner de fête. Le lundi 25 mai, deuxième et dernier jour de Shavuot, se passe en prières et en lectures des textes saints. La fête se termine au coucher du soleil. Shavuot sameh (bonne fête de Shavuot) à tous nos compatriotes de confession juive !
Keywords: Judaïsme -- Djerba

Les borjs côtiers de Djerba : Dragut, fortins et patrimoine en péril - Bourial, Hatem (Webdo, 2015)
Keywords: Monuments -- conservation -- Djerba

Pèlerinage juif en terre d’Islam – La Hiloula de la Ghriba aura lieu du 13 au 18 mai 2014 - Bourial, Hatem (Webdo, 2013)
Keywords: Judaïsme -- Djerba

L’ibadisme à la base de la spécificité de l’identité des Jerbiens - Maamer, Kérim (la troisième république tunisienne, 2013)

Il faut sauver Djerba maintenant ! - Bourial, Hatem (Webdo, 2013)
Un petit pas en avant vient d’être fait à Djerba. Mais pour cela, il aura fallu l’explosion de colère d’octobre dernier, lorsque la population du paisible village de Gallala avait grondé pour faire entendre sa voix. On se souvient avec tristesse de ces deux journées d’émeute, de ces destructions et de toute la violence qui avait déferlé sur l’ile de Djerba. Quelques mois plus tard, les solutions pour la gestion des déchets, de plus en plus nombreux, commencent à trouver leur chemin et Djerba commence à panser ses plaies en matière d’environnement. Pourtant, le problème des déchets demeure entier et la pollution s’installe insidieusement dans les villes principales de Djerba mais aussi dans les campagnes les plus éloignées. Il est à ce titre désolant et à peine croyable de constater que dans le triangle rural Sidi Jmour – Bazim – Sidi Hachan, les décharges à ciel ouvert se sont multipliées, loin des regards, à cause de l’indiscipline des riverains et le laisser-aller général. A Djerba, il n y a pas que les déchets qui posent problème. L’équilibre écologique fragile de l’île subit les assauts du béton, du tourisme intensif et de l’urbanisation sauvage. En fait, l’île est quasiment défigurée et semble avoir perdu sa vocation de jardin miraculeux. Plusieurs actions associatives et aussi gouvernementales sont aujourd’hui entreprises mais que peuvent-elles face à la gabegie généralisée ? L’eau, rare et précieuse, est gaspillée sans vergogne, les menzels historiques sont remplacés par des buildings sans identité, les sentiers ruraux sont fragilisés par les quads et consorts qui s’infiltrent partout et, last but not least, ici aussi des zaouias ont été attaquées et détruites. Djerba souffre, c’est un fait. Pire, le seul site encore préservé de l’île commence à subir les assauts du béton. Tout le long de la plage qui mène jusqu’à Ajim, le rivage est carrément envahi par les déchets de toutes sortes. Ainsi, la seule plage dont les locaux font usage a pris une allure de dépotoir. On pourrait multiplier les exemples, établir une cartographie des dangers et demander des actions urgentes. Cela ne suffira pas et le projet d’île-jardin pour lequel le gouvernement promet de dépenser 16 millions d’euros tarde à voir le jour. Les menaces qui pèsent sur Djerba ne sont pas seulement écologiques. On constate ici et là des surenchères intégristes qui n’hésitent plus à s’exprimer haut et fort. Assistons-nous à un retour de l’intolérance dans ce havre béni des dieux ? En ce sens, cela constituerait un terrible recul. Pour l’heure, la nouvelle saison touristique sera certainement placée sous le signe de l’affluence libyenne et algérienne. Encore une fois, ce sont nos voisins qui vont sauver les meubles. Heureusement ! Encore faudrait-il, une fois pour toutes, réfléchir sur le destin futur de Djerba. Il est plus que temps : il faut sauver Djerba maintenant !
Keywords: Tourisme -- Djerba

Flagrant délit d'amnésie - Bourial, Hatem (Webdo, 2011)
Keywords: Attentats -- Djerba -- 2002

SECTS IN ISLAM- writing "Al Khawarij"---also known as Ibadhi (Beautiful Muslimah, 2011)
Keywords: Kharijisme

Djerba : Il était une fois l'hôtel du Lotos - Bourial, Hatem (Webdo, 2020)
L’hôtel du Lotos est l’un des premiers établissements à avoir ouvert ses portes à Djerba. Non loin du port de Houmt Souk, cet hôtel existe encore de nos jours alors que cette carte ancienne le représente au milieu des années soixante. Cet hôtel avait été fondé par un Grec dont le nom est devenu mythique. …
Keywords: Emigration -- Grèce -- Djerba

Pêcheurs d'éponges - Bourial, Hatem (Webdo, 2020)
A Djerba, Zarzis et ailleurs dans le golfe de Gabés, la pêche aux éponges est une tradition qui perdure. Dans le temps, des plongeurs allaient dans les profondeurs pour extraire les éponges. En général, ils plongeaient en apnée. Toutefois, des scaphandriers travaillaient aussi sur ce type de pêche. Nos photos de l’agence Getty montrent des …
Keywords: Pêche -- Djerba

Djerba : Les habits neufs de l'église de Houmt-Souk - Bourial, Hatem (Webdo, 2020)
Longtemps fermée, l’église de Houmt Souk à Djerba a réouvert ses portes pour le culte catholique au tournant du nouveau siècle. Une vingtaine d’années plus tard vient le temps de la restauration pour cette église dédiée à Saint-Joseph. Entreprise par l’Archevêché de Tunis, cette restauration bénéficie de l’appui de l’Association pour la sauvegarde de l’île …
Keywords: Christianisme -- Djerba

Ghriba, Echo de Djerba et mémoire de Lotfi Jeriri - Bourial, Hatem (Webdo, 2020)
Keywords: Judaïsme -- Djerba

Djerba : Le pèlerinage de la Ghriba aurait eu lieu aujourd'hui - Bourial, Hatem (Webdo, 2020)
C’est aujourd’hui au crépuscule que commence la fête juive de Lag Be Omer à l’occasion de laquelle est organisé le pèlerinage de la Ghriba. C’est en effet trente-trois jours après Pessah que se déroule le pèlerinage annuel qui est considéré comment un temps fort du judaisme tunisien. Cette solennité qui est également dédiée au rabbin …
Keywords: Judaïsme -- Djerba

Patrimoine : A Djerba, la synagogue Beit Shalom - Bourial, Hatem (Webdo, 2020)
Parmi les nombreuses synagogues de Djerba, ce lieu de culte se caractérise par des proportions modestes et une notoriété bien établie. Cette synagogue Beit Shalom se trouve à Hara Kebira, le quartier historique des juifs djerbiens. Elle est peu connue car elle est sise à l’intérieur d’une « yeshiva » c’est à dire d’une école d’apprentissage de …
Keywords: Judaïsme -- Djerba

À la Ghriba de Djerba : Une prière pour Bourguiba - Bourial, Hatem (Webdo, 2020)
Durant tout le règne de Ben Ali et malgré la volonté de ce dernier de faire de l’ombre à Bourguiba, cette plaque n’a pas été descellée ou éloignée des regards. Massive écrite en arabe et en français, cette plaque en marbre se trouve à l’entrée de la synagogue de la Ghriba à Djerba. Elle exprime …
Keywords: Judaïsme -- Djerba

Un invité de marque : Anatoli Karpov à Djerba - Bourial, Hatem (Webdo, 2020)
Djerba accueille jusqu’au 24 février un festival international du jeu d’échecs avec la participation de nombreux invités de prestige. Parmi les invités du festival, Anatoli Karpov fait figure de symbole. Champion du monde et grand maître international, Karpov possède l’un des plus grands palmarès de l’histoire du jeu d’échecs. Il a régné sur cette discipline …
Keywords: Vie culturelle -- Djerba

Djerba: En neuf photos, l'église grecque orthodoxe Saint-Nicolas - Bourial, Hatem (Webdo, 2020)
Non loin de la Marina, à Houmt-Souk, la petite église Saint-Nicolas se souvient encore de la communauté grecque de Djerba. Présents en nombre jusqu’aux années cinquante, les Grecs de Djerba sont les descendants de pêcheurs d’éponges et de poulpes qui se sont installés dans l’île à la fin du dix-neuvième siècle. C’est de cette époque …
Keywords: Emigration -- Grèce -- Djerba

Judaïsme tunisien : A Djerba, la synagogue des Cohanim - Bourial, Hatem (Webdo, 2020)
Keywords: Judaïsme -- Djerba

Le bilan du sommet de Djerba passé en revue entre Jerandi et Desiree N. Herrera - African Manager (2022)
Le ministre des Affaires étrangères, de la Migration et des Tunisiens de l'étranger, Othman Jerandi a reçu, mardi, le conseiller politique et diplomatique
Keywords: Francophonie -- Djerba

Le site de Ras R’mal à Djerba, théâtre de tous les outrages - Bouabid, Naceur (Kapitalis, 2022)
La situation dans laquelle se trouve, aujourd’hui encore, la flèche sableuse de Ras R’mal à Djerba est regrettable, déplorable et révoltante. Voilà pourquoi… Par Naceur Bouabid * Cette situation est regrettable au vu du sort ingrat et réducteur réservé à ce merveilleux site naturel d’une rare beauté et aux spécificités paysagères exceptionnelles, indigne d’une zone humide...
Keywords: Crises environnementales -- Djerba

Tunisie : les dessous peu ragoûtants du pèlerinage juif de la Ghriba - Bomse, Audrey; Chabbi, Nizar (Kapitalis, 2022)
Nizar Chabbi nous a fait parvenir ce texte, co-écrit avec Audrey Bomse, avocate juive américaine de Floride, publié une première fois en mai 2014, et réécrit récemment, où il évoque les dessous peu ragoûtants du pèlerinage juif à la synagogue de la Ghriba, à Djerba, en Tunisie. La normalisation du président Kaïs Saïed, le plus...
Keywords: Judaïsme -- Djerba

الواجهة الدينية لعمان.. السلام الطائفي وإرهاب السلطة على لسان المفتي (مواطن, 2022)
تحتل عمان المرتبة الأولى بين دول الخليج في تمثيل الأقليات، حسب مؤشر المشاركة السياسية في الخليج الصادر عن مركز البيت
Keywords: Tolérance religieuse -- Oman

ندوة علمية حول موضوع جهود الشيخين الحاج محمد نوح مفنون والحاج محمد ابصير (موقع مجلس أعيان آت يسجن, 2018)
الحاج محمد بن بنوح نوح مفنون والحاج محمد بن عمر ابصير وجهادهما " المجتمع بين الوفاء للمبادئ والتعامل مع التحديات " موضوع ندوة علمية تحت إشراف حلقة العزابة

Le Mzab de l’extinction. Une idéalité à reprendre en sous-œuvre - Benkoula, Sidi Mohammed el Habib (Les carnets de l'IREMAM, 2021)
Keywords: Urbanisme -- Mzab

Le décès de Moufida Tlatli (Africultures, 2021)
Keywords: Biographies -- Djerba -- 20e siècle

La Saison des hommes - Barlet, Olivier (Africultures, 2000)
Les Silences du Palais avaient résonné très fort en chacun et trouvé plus de 200 000 spectateurs en France. Ce deuxième film, guidé par les doutes et les interrogations de sa propre fille devenue adolescente, développe cette réflexion autobiographique. Il est traversé de scènes magnifiques et émouvantes, comme celle de ces femmes lavant leur hennéLire la suite
Keywords: Emigration -- Djerba

Parcours de femmes : Moufida Tlatli, Ingrid Sinclair et Nadine Labaki (Africultures, 2008)
Le 20 mai sur le Pavillon des Cinémas du Sud au Festival de Cannes 2008, Serge Toubiana, Directeur Général de la Cinémathèque Française et Bouchra Khalili, réalisatrice, qui dirige la Cinémathèque de Tanger, ont animé une table ronde réunissant à l’occasion des 40 ans de la Quinzaine des Réalisateurs Moufida Tlatli (Tunisie), Ingrid Sinclair (Zimbabwe)Lire la suite
Keywords: Cinéma -- Djerba

L'alternative démocratique dans le cinéma des femmes en Tunisie (1970-2015) - Rouxel, Mathilde (Africultures, 2016)
Sur l'oeuvre de Moufida Tlatli
Keywords: Cinéma -- Djerba

ليبيا … من فتنة إلى أخرى - الجورشي, صلاح الدين (المغاربي للدراسات والتحاليل, 2017)
أن يبقى الخلاف بين الفرقاء الليبيين سياسيا، فذلك أمر يمكن معالجته في يوم من الأيام، لك
Keywords: Polémique wahhabite -- 2000-....

ليبيا: التحريض ضد أقلية دينية: يجب إلغاء الفتوى التمييزية (Human Rights Watch, 2017)
قالت "هيومن رايتس ووتش" اليوم إن على "اللجنة العليا للإفتاء"، المرتبطة بإحدى الحكومات الليبية المتنافسة، أن تلغي فتوى شرعية تمييزية تتهم أتباع الإباضية في ليبيا بـ "الانحراف" والالتزام بعقائد "كفرية". لم ترد بعد الحكومة المرتبطة باللجنة، الحكومة المؤقتة التي تتخذ من البيضاء مقرا لها، أو مجلس النواب علنا ​​على هذه الفتوى.
Keywords: Polémique wahhabite -- 2000-....

الشيخ ابن باديس وعلاقته بالحركة الإصلاحية بوادي ميزاب - ناصر, محمد صالح (موقع الشيخ عبد الحميد بن باديس, 2012)
Keywords: Réformisme -- Mzab

The Forgotten Generation of Muscat: Reconstructing Omani National Identity After the Zanzibar Revolution of 1964 - Patterson, Molly (The Middle Ground Journal, 2013)

De l’urbanisation sans urbanistes à l’urbanisation sans visionnaires - Benkoula, Sidi Mohammed el Habib (Les carnets de l'IREMAM, 2014)
Je crois que mes propos concernant cette question de l’urbanisation sans vision en Algérie à partir des exemples qui reviennent souvent dans la littérature architecturale diffusée, le M’Zab et le Gourna par exemple, n’auront de sens que si je les introduis par quelques détours du côté des approches … Continuer la lecture de De l’urbanisation sans urbanistes à l’urbanisation sans visionnaires →
Keywords: Urbanisme -- Mzab

Une si longue Antiquité tardive : À propos des derniers chrétiens d’Afrique du Nord médiévale - Nsiri, Mohamed Arbi (Carnet de recherche de l'IPRA, 2018)
Le Maghreb est aujourd’hui une région qui revendique, à juste titre, sa double appartenance à la communauté musulmane et au monde arabe. Or cette région, après bien des vicissitudes, est pris la lointaine succession d’une Africa qui, depuis la chute de la Carthage punique, appartenait aussi sûrement au monde romain puis au monde chrétien. Comment donc expliquer cette métamorphose culturelle,...
Keywords: Christianisme -- Afrique du nord

The Religion of Oman — Ibadism - Singhal, Reema (Lesser-known Religions, 2012)
While most of us have heard this word, we understand its meaning, correctly so, to be a sincere prayer (ibadat). And it is mostly in reference to Islam. What I discovered some while back is that Ib…
Keywords: Ibadisme -- Oman

“Oman after Qaboos will be more dependent on the UK and the US” - Valeri, Marc (My East-West, 2015)
Marc Valeri is Senior Lecturer in Political Economy of the Middle East, Director of the Centre for Gulf Studies at the University of Exeter, in the United Kingdom. An expert on the Sultanate that w…
Keywords: Vie politique -- Oman -- 1970-2020

Marguerite van Berchem : une figure emblématique - Allemann, Marie (ICRC History, 2016)
Keywords: Archéologie -- Sedrata

Oman: Will the Imamate Return? - Katz, Mark N. (Travels and Observations, 2014)
Some twenty years ago, I wrote up the following notes for myself after reading John C. Wilkinson’s The Imamate Tradition of Oman (Cambridge University Press, 1987): While Omanis are virtually all M…
Keywords: Vie politique -- Oman -- 1970-2020

The undecided Sultanate: tolerance, challenge and sovereignty - Kronenwerth, Dorian (2015)
Keywords: Tolérance religieuse -- Oman

الفكر السّياسي الإباضي ..مناخ إنسانيّ متجدّد - ولد العروسي, الطيب (صحيفة أثير الإلكترونية, 2014)

Oman, a Land Apart - Pereltsvaig, Asya (Languages Of The World, 2015)
[Continuing with the theme of the Arabic-speaking world, here’s a post originally published in June 2012] Much attention in the conventional media has been focused on the “Arab Spring” events of the past year and a half. However, not all Arab countries have participated in the turmoil. One notable exception is Oman, currently one of […]
Keywords: Linguistique -- Oman

Kharijism in Islamic North Africa (700-900): A Summary Overview - Ballandalus (Ballandalus, 2014)
In the traditional framework of Islamic historiography, the Kharijites are constructed within the broader narrative as the very antithesis of a centralizing Islamic polity and an increasingly “orth…
Keywords: Kharijisme

Prophetic Traditions about the Virtues of the Berbers in the North African Ibadi Tradition - Ballandalus (Ballandalus, 2013)
The following is excerpted from Ibn Sallām, Kitāb fīhi bada’ al-islām wa sharā’i‘ al-dīn, pp. 121–125. This book, written by an Ibadi from the Tripolitania region, is the first-known historical acc…

Rustamid Dynasty: An Ibadi State in North Africa (776-909) - Ballandalus (Ballandalus, 2012)
The Rustamids were an Ibādī dynasty, of Persian origin, which reigned from Tāhart (in what is now Algeria) 161-296/776-909. The following summary and narrative of the political history of this fasc…
Keywords: Dynastie rustumide

An Early Kharijite Critique of the Azariqa: Najda ibn Amir’s Letter to Ibn al-Azraq - Ballandalus (Ballandalus, 2014)
The following is an important, yet little known, document. It is one of the earliest Kharijite critiques of the radical movement of the Azariqa. It was written by Najda ibn ‘Āmir (d. 692), the foun…
Keywords: Kharijisme

Conflicts and Harmony in Zanzibar - Mathews, Nathaniel (2008)
Finished Ali Muhsin Al Barwani's memoirs today-- Conflicts and Harmony in Zanzibar Sheikh Ali translated the Holy Quran into Swahili, a co...
Keywords: Zanzibar

L’aménagement du territoire et l’identité nationale à Oman - Klinger, Thibaut (Centre Français de Recherche de la Péninsule Arabique, 2016)
Keywords: Urbanisme -- Oman

Oman : une Oasis pacifique dans une région en feu - Elhusseini, Fadi (La Revue Internationale, 2016)
Dans une région instable et ou les conflits abondent, un pays ressort indemne de ce chaos. Il est dit qu'Oman non seulement ressort intact des soubresauts du printemps arabe, mais s'est aussi protégé de l'état de polarisation tendu qui a détourné la région entière. La position d'Oman vis à vis des questions régionales diverses était apparemment pacifique et différente du reste des monarchies du Golfe. Cependant, derrière cette position pacifique et unique se trouve un rôle actif caché que beaucoup ignorent.

La Libye en 2014 : du long « one man show » de Qadhafi, aux premiers pas de la société plurielle - Burgat, François (Les carnets de l'IREMAM, 2014)
ERC WAFAW – CNRS, IREMAM « Le pouvoir au peuple », « Le peuple en armes » … « Des comités populaires partout »… Il est difficile de ne pas adopter la boutade qui circule à Tripoli trois ans après le soulèvement du 17 février 2011. L’utopique démocratie directe prônée par Qadhafi dans son petit Livre Vert serait-elle devenue réalité ? Si … Continuer la lecture de La Libye en 2014 : du long « one man show » de Qadhafi, aux premiers pas de la société plurielle →

Ibadi ahadith (Hajarmulder's Blog, 2008)
Ibadi Islam is mainly found in Oman and also in some places of eastern African countries like Somalia, further in Algeria, Tunisia and Libya. Ibadism’s founding figures are Jabir ibn Zayd and…
Keywords: Hadith

Libya: Government Using Landmines in Nafusa Mountains (Human Rights Watch, 2011)
(Cairo) - Libyan government forces placed more than 150 antipersonnel landmines in at least one location in the Nafusa Mountains, Human Rights Watch said today. Human Rights Watch visited the site, inspected mines that had been removed, and interviewed the rebel fighters who removed them.

Sultanat d’Oman : la « troisième voie » pour en finir avec la bipolarisation - Sassine, Georges (Afrique Asie, 2014)
Un visiteur du Sultanat d’Oman, en pleine saison touristique, ne peut qu’être frappé par les manifestations populaires festives quotidiennes à l’occasion de la fête nationale du pays. Une fête quelque
Keywords: Politique étrangère -- Oman -- 1970-2020

Saudi Arabia and Oman Have Different Experiences With Extremism - Grappo, Gary (Fair Observer, 2015)
Saudi Arabia and Oman possess differing national identities, varied social and cultural roots, and divergent approaches to tolerance that may explain...
Keywords: Zanzibar

Ibadi Shamelessly Defends Haruriya Kharijites (2018)

Nel deserto spunta l'oasi eco-compatibile - Beretta, Ilaria (Mondo e Missione, 2016)
Da vent’anni l’oasi storica di Tafilelt nel deserto algerino si è trasformata in un villaggio eco-compatibile. Con pannelli solari, raccolta differenziata e parco naturalistico, l’eco-city del Sahara è ora un modello di città all’avanguardia per l’intero continente africano.   Nel … Continua
Keywords: Urbanisme -- Mzab

دراسات استشراقية في المذهب الأباضي (2014)
دراسات استشراقية في المذهب الأباضيقراءة في السلسلة الصادرة عن دار الغشام؛ بتحرير عبدالرحمن السالميبقلم &nbs

Her hometown is not where she lives, but a Tunisian island - Temzini, Lina (Youth Journalism International, 2019)
Djerba, TUNISIA – My hometown Guellala is a place of wonders, where love, compassion and kindness prevail. It’s a place that means so much to me, and even though I have never actually lived there, I think of it as home. It’s a small town on the beautiful island of Djerba, an island located off […]
Keywords: Récits de voyage -- Djerba

ناجية الوريمي: التفكيك عملية ضروية تحدد ما يمكن أن يتواصل وما يجب أن يحفظ في المتاحف - فرج, ريتا; الوريمي بوعجيلة, ناجية (2019)

القصص القومي - الباروني, زعيمة سليمان (Tamatart, 2012)

Quel avenir pour le Sultanat d'Oman ? - Vagile, Juliette (Aujourd'hui la Turquie, 2014)
Les rumeurs de cancer et la raréfaction des apparitions du Sultan d’Oman inquiètent les citoyens de son pays : Qabous ben Saïd, n’ayant pas d’enfant, n’a effectivement pas de descendance directe, …
Keywords: Vie politique -- Oman -- 1970-2020

In Libya, the Amazighs fight for their rights, but risk getting caught in the country's ongoing and bloody conflict (Fanack.com, 2019)
Amazighs in Libya range between less than 200,000 and up to 1.5 million, which would represent around a quarter of Libya’s 6.75 million population. Some estimate a more realistic figure between 500,000 and 750,000.
Keywords: Vie politique -- Libye -- 2011-....

Vermondo Brugnatelli écrit: “Pouvoir assassin!” Lo slogan divenuto la colonna sonora della « Primavera nera » del 2001 torna - Siwel, Aneghmas (2019)
MILAN (SIWEL)—"Fekhar muore in cella, i berberi si mobilitano", a titré aujourd'hui, le 31/05/2019, le quotidien italien "ILMANIFESTO" , dont l'auteur n'est

Une prison Daeshienne à Ghardaia… L’incroyable témoignage de Maître Dabouz ! - Dabouz, Salah (Ma Revue De Presse DZ, 2019)
« On tourne le dos à nos frères de Ghardaia. On les laissent subir seuls les arrestations arbitraires et l’harcèlement judiciaire. Puis on les blâmera demain s’ils demandent leur autonomie ».…
Keywords: Conflits -- Mzab

فتوى «تكفير» الإباضيين تثير موجة استنكار واسعة في ليبيا - سلمان, حسن (القدس العربي, 2017)
تونس ـ «القدس العربي» من حسن سلمان: استنكر سياسيون وحقوقيون ليبيون «فتوى» جديدة صادرة عن هيئة أوقاف حكومة «طبرق» في الشرق، تنص على «تكفير» أتباع المذهب الإباضي في البلاد، مطالبين بحل هذه الهيئة وحماية الطائفة الإباضية في البلاد، فيما دعت «دار الإفتاء الليبية» في طرابلس إلى الابتعاد عن هذا النوع من الخطاب الذي قد يتسبب بـ»فتنة مذهبية» في البلاد.
Keywords: Nukkarisme

Perfect Pair, Ghadames Libya - Arebi, Naziha (2014)
Keywords: Musique -- Ghadamès

The Little-Known yet Storied Past Linking Oman and Zanzibar - Bodetti, Austin (Inside Arabia, 2021)
Only a few scholars have explored the shared past of Oman and Zanzibar. Nonetheless, culture, history, and religion continue to bind the two.
Keywords: Relations -- Oman -- Afrique de l'Est

Sultan Bargash and Zanzibar’s cosmopolitan modernity (SSRC The Immanent Frame, 2021)
The context Stone Town Café in the old city of Zanzibar is located in the middle of the most stunning buildings with gorgeous lacy balconies made of Indian teakwood and...
Keywords: Vie culturelle -- Zanzibar

Islamisation et constitution des élites africaines (8e-16e siècles). Note sur l’œuvre inachevée de Pierre-Philippe Rey - Berger, Laurent (Histoire Globale, 2010)

A few verses by Ahmad Rafig al-Mahdawi (The Silphium Gatherer | مجمّع سلفيوم, 2016)
The ‘national poet’ of Libya, Ahmad Rafig al-Mahdawi (احمد رفيق المهدوي), wrote a poem entitled أنا ساكت “I am silent” during the de-colonization of Libya and the struggle f…
Keywords: Poésie -- Djebel Nefousa

Professors promote global citizenship in Oman, Egypt (The Etownian, 2011)
Three faculty members from Elizabethtown College have been chosen to join members from other local colleges as participants in the 2011-2012 Faculty International Scholarship Seminar (FISS). Six pa…

The sultanate of Oman: true Arabia and zero terrorism - Maksimovic, Sandra (SARAH MAX RESEARCH, 2016)
WHY IS THIS ABSOLUTE MONARCHY, BASED ON  IBADISM   A GOOD EXAMPLE FOR ALL MUSLIM COUNTRIES TO FOLLOW ? This exotic country, located on Arabic Peninsula with the 5000 years old history and the best …
Keywords: Politique étrangère -- Oman -- 1970-2020

Comment vivent les derniers juifs de Djerba? - Cheslow, Daniella (JForum, 2018)
Djerba, l’avenir de l’une des dernières et plus anciennes communautés juives du monde arabe est incertain
Keywords: Judaïsme -- Djerba

WORKSHOP : « Connectivités djerbiennes. Globalisations méditerranéennes des Juifs de Djerba » (26 novembre 2020) (CRFJ.org, 2020)
Jeudi 26 novembre 2020 - Le projet vise à entamer une enquête exploratoire et pluridisciplinaire sur les Juifs de Djerba en Méditerranée (Djerba, Marseille, Israël). Il s’appuie sur et rend hommage au travail de Lucette Valensi, et à son étude monographique (avec Abraham Udovitch, 1984) des « Last
Keywords: Judaïsme -- Djerba

بطولات تونسية تاريخية: ذكرى معارك جربة 1432 ضد الأرغونيين (القومية التونسية, 2019)
رغم الود الظاهر في العلاقات بين الحفصيين و الأرغونيين، إلا أن المراسلات المملوءة بعبارات الود
Keywords: Invasions chrétiennes -- Djerba

Valerie J. Hoffman, The Essentials of Ibāḍī Islam, Syracuse, Syracuse University Press, 2012, xii + 344 p. - Prevost, Virginie (Maghribadite, 2012)
Valerie J. Hoffman, The Essentials of Ibāḍī Islam, Syracuse, Syracuse University Press, 2012, xii + 344 p. Valerie J. Hoffman a publié ces dernières années plusieurs articles sur les ibadites d’Oman et de Zanzibar aux XIXe et XXe siècles. Son dernier livre porte sur la théologie ibadite qu’elle souhaite rendre accessible au grand public … Continuer la lecture de Le nouveau livre de Valerie Hoffman: une lecture de Virginie Prevost →
Keywords: Zanzibar

Où en est le volume sur Sedrata ? - Aillet, Cyrille (Maghribadite, 2015)
Beaucoup de collègues et d’amis, de part et d’autre de la Méditerranée, sont impatients de lire le volume que nous avons dirigé avec Patrice Cressier et Sophie Gilotte sur Sedrata, histoire et archéologique d’un carrefour du Sahara médiéval. Il est terminé, a été relu et approuvé par deux examinateurs anonymes, et se trouve donc en … Continuer la lecture de Où en est le volume sur Sedrata ? →
Keywords: Archéologie -- Sedrata

Qu'est-ce qu'un ksar pour un Mozabite - Gueliane, Nora (Le carnet de recherche du Centre Jacques Berque, 2019)
Keywords: Urbanisme -- Mzab

Die gefährdete antike Stadt Meninx auf Djerba - Quist, Otto (archaeologieblog.de, 2016)
Keywords: Archéologie -- Djerba